Slurry composition for positive electrode of non-aqueous secondary battery, positive electrode for non-aqueous secondary battery, and non-aqueous secondary battery
By using a slurry composition coated with olivine lithium iron phosphate particles and specific polymers, the problems of insufficient dispersion, adhesion and water removal of the positive electrode composite material layer of the secondary battery are solved, and more efficient Electrode material combination and performance improvement.
Patent Information
- Application Number
- CN202380051395.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-07-03
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, there is room for improvement in the dispersion, adhesion and water removal properties of the slurry composition for the positive electrode of the secondary battery, which affects the performance of the secondary battery.
A slurry composition for a nonaqueous secondary battery positive electrode is used, which includes carbon coating coated with olivine lithium iron phosphate particles and a polymer containing a specific proportion of acid group-containing monomer units.
The dispersion of the slurry composition is significantly improved, and the adhesion and water removal of the formed positive electrode composite material layer are enhanced, thereby reducing the internal resistance of the secondary battery.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to a slurry composition for a positive electrode of a non-aqueous secondary battery, a positive electrode for a non-aqueous secondary battery, and a non-aqueous secondary battery. Background Art
[0002] Non-aqueous secondary batteries such as lithium-ion secondary batteries (hereinafter sometimes referred to as "secondary batteries") are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and have been used in a wide range of applications. Therefore, in recent years, with the goal of further improving the performance of secondary batteries, research has been conducted on the improvement of battery components such as electrodes.
[0003] Here, the electrode for secondary battery usually has an electrode composite material layer. Moreover, the electrode composite material layer can be formed by, for example, dispersing an electrode active material and a polymer serving as a binder (binder) in a dispersion medium to form a slurry-like composition (slurry composition) on a current collector and drying it.
[0004] Therefore, in recent years, attempts have been made to improve the components of a slurry composition for forming an electrode composite material layer in order to further improve the performance of secondary batteries (for example, refer to Patent Document 1).
[0005] For example, Patent Document 1 discloses a water-soluble polymer as a binder, which contains 50 to 95% by mass of structural units from ethylenically unsaturated carboxylic acid ester monomers, 5 to 50% by mass of structural units from ethylenically unsaturated carboxylate monomers, and has a weight average molecular weight of 500,000 or more. Moreover, according to Patent Document 1, it is reported that a positive electrode aqueous composition containing the above-mentioned water-soluble polymer as a binder, a compound having an olivine structure such as lithium iron phosphate as a positive electrode active material, and water as a dispersion medium can be used as a slurry composition for forming a positive electrode for a secondary battery, and the positive electrode aqueous composition does not damage the dispersibility and viscosity adjustment function and improves the electrode formability, substrate adhesion, and flexibility.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent document 1: International Publication No. 2012 / 008539. Summary of the invention
[0009] Problem that the invention aims to solve
[0010] However, the dispersibility of the above-mentioned prior art slurry composition still has room for improvement.
[0011] Furthermore, the above-mentioned prior art slurry composition also has room for improvement in terms of improving the adhesion of the formed positive electrode composite material layer to strengthen the adhesion between the positive electrode composite material layer and the current collector and the adhesion between the components in the positive electrode composite material layer (for example, between the positive electrode active materials).
[0012] In addition, from the viewpoint of suppressing the generation of gas inside the battery cell of the secondary battery to reduce the internal resistance of the secondary battery, the battery components such as the electrode for forming the secondary battery are sometimes dried before assembling the secondary battery. Therefore, the electrode composite material layer of the secondary battery electrode requires easy removal of water, that is, excellent dehydration. However, the dehydration of the positive electrode composite material layer formed using the slurry composition of the above-mentioned prior art also has room for improvement.
[0013] Therefore, an object of the present invention is to provide a non-aqueous secondary battery positive electrode slurry composition that has excellent dispersibility and can enable a positive electrode composite material layer to exhibit excellent adhesion and dehydration properties.
[0014] Furthermore, an object of the present invention is to provide a positive electrode for a non-aqueous secondary battery having a positive electrode composite material layer capable of exhibiting excellent adhesiveness and water-removing properties.
[0015] Furthermore, an object of the present invention is to provide a non-aqueous secondary battery having the positive electrode for a non-aqueous secondary battery.
[0016] Solutions for solving problems
[0017] The inventors have conducted in-depth research for the purpose of solving the above problems. Then, the inventors found that if the non-aqueous secondary battery positive electrode slurry composition is as follows, the non-aqueous secondary battery positive electrode slurry composition comprises: olivine-type lithium iron phosphate particles, at least a portion of the surface of which is coated with a carbon coating, and the content of weakly acidic groups on the surface is within a specified range; and a polymer containing acidic group-containing monomer units in a specified ratio, then the dispersibility is excellent and the adhesion and dewatering properties of the positive electrode composite material layer formed using the slurry composition can be improved, thereby completing the present invention.
[0018] That is, the object of the present invention is to advantageously solve the above-mentioned problems. The present invention is [1] a slurry composition for a positive electrode of a non-aqueous secondary battery, comprising: carbon-coated olivine-type lithium iron phosphate particles in which at least a portion of the surface of the olivine-type lithium iron phosphate particles is coated with a carbon coating; and a polymer X containing 3% by mass or more and 40% by mass or less of an acidic group-containing monomer unit, wherein the content of weakly acidic groups on the surface of the carbon-coated olivine-type lithium iron phosphate particles is 5 μmol / g or more and 15 μmol / g or less.
[0019] The non-aqueous secondary battery positive electrode slurry composition comprising olivine-type lithium iron phosphate particles whose surfaces are at least partially coated with a carbon coating and whose surface weakly acidic group content is within a specified range and a polymer containing an acidic group-containing monomer unit in a specified ratio has excellent dispersibility, and the positive electrode composite material layer formed using the slurry composition can exhibit excellent adhesion and water removal properties.
[0020] In the present invention, the content of weakly acidic groups on the surface of the carbon coating layer-coated olivine-type lithium iron phosphate particles can be measured using the method described in Examples of the present specification.
[0021] In the present invention, a polymer “containing a monomer unit” means that “a polymer obtained using the monomer contains a repeating unit derived from the monomer”.
[0022] Furthermore, in the present invention, the content ratio (mass %) of each monomer unit contained in the polymer can be expressed as 1 The determination was carried out by nuclear magnetic resonance (NMR) methods such as H-NMR.
[0023] [2] In the non-aqueous secondary battery positive electrode slurry composition of [1] above, the carbon coating layer preferably has a G / D ratio of 0.4 or more and 0.770 or less.
[0024] When the G / D ratio of the carbon coating layer of the carbon coating layer-covered olivine-type lithium iron phosphate particles is within the above-specified range, the dispersibility of the slurry composition for a nonaqueous secondary battery positive electrode can be further improved and the internal resistance of the nonaqueous secondary battery can be reduced.
[0025] In the present invention, the G / D ratio of the carbon coating layer can be measured using the method described in Examples of the present specification.
[0026] [3] In the nonaqueous secondary battery positive electrode slurry composition of [1] or [2], the acidic group-containing monomer unit preferably contains at least one of a carboxylic acid group-containing monomer unit and a sulfonic acid group-containing monomer unit.
[0027] If the polymer X contains at least one of a carboxylic acid group-containing monomer unit and a sulfonic acid group-containing monomer unit as the acidic group-containing monomer unit, the adhesiveness of the positive electrode composite material layer can be further improved.
[0028] [4] In the nonaqueous secondary battery positive electrode slurry composition according to any one of [1] to [3], the polymer X preferably further contains 55% by mass or more and 90% by mass or less of a hydroxyl group-containing acrylic acid ester monomer unit.
[0029] If the polymer X further contains a hydroxyl group-containing acrylic acid ester monomer unit at the above-specified content ratio, the adhesiveness of the formed positive electrode composite material layer can be further improved.
[0030] [5] In the nonaqueous secondary battery positive electrode slurry composition according to any one of [1] to [4], the weight average molecular weight of the polymer X is preferably 50,000 or more and less than 500,000.
[0031] When the weight average molecular weight of the polymer X is within the above-specified range, the dispersibility of the slurry composition for a non-aqueous secondary battery positive electrode and the adhesiveness of a positive electrode composite material layer formed using the slurry composition can be further improved.
[0032] The weight average molecular weight of the polymer X can be measured by the method described in Examples of the present specification.
[0033] [6] The nonaqueous secondary battery positive electrode slurry composition according to any one of [1] to [5] above preferably further contains a particulate polymer Y having a hydrophilic group.
[0034] If the non-aqueous secondary battery positive electrode slurry composition further contains a particulate polymer Y having a hydrophilic group, the dispersibility of the slurry composition and the adhesiveness of the positive electrode composite material layer formed using the slurry composition can be further improved.
[0035] [7] In the non-aqueous secondary battery positive electrode slurry composition of [6], the content of the particulate polymer Y is preferably 0.5 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the carbon coating layer-covered olivine-type lithium iron phosphate particles.
[0036] If the content of the particulate polymer Y containing a hydrophilic group in the non-aqueous secondary battery positive electrode slurry composition is within the above-specified range, the dispersibility of the slurry composition and the adhesiveness of the positive electrode composite material layer formed using the slurry composition can be further improved, while the softness of the positive electrode composite material layer can be sufficiently high.
[0037] [8] The nonaqueous secondary battery positive electrode slurry composition according to any one of [1] to [7] may further contain a conductive material including at least one of carbon nanotubes and a particulate conductive material.
[0038] In addition, the object of the present invention is to advantageously solve the above-mentioned problems. The present invention is [9] a positive electrode for a non-aqueous secondary battery, which has a positive electrode composite material layer formed using the slurry composition for a non-aqueous secondary battery positive electrode according to any one of the above [1] to [8].
[0039] The positive electrode for a nonaqueous secondary battery of the present invention has a positive electrode composite material layer formed using any of the above-mentioned slurry compositions for a nonaqueous secondary battery positive electrode and capable of exhibiting excellent adhesiveness and water removal properties.
[0040] Furthermore, an object of the present invention is to advantageously solve the above-mentioned problems. The present invention is
[10] a non-aqueous secondary battery comprising the positive electrode for a non-aqueous secondary battery of [9] above.
[0041] The nonaqueous secondary battery of the present invention includes any one of the above-described positive electrodes for nonaqueous secondary batteries, and therefore, for example, internal resistance can be reduced and battery characteristics are excellent.
[0042] Effects of the Invention
[0043] According to the present invention, it is possible to provide a non-aqueous secondary battery positive electrode slurry composition that has excellent dispersibility and can enable a positive electrode composite material layer to exhibit excellent adhesiveness and water removal properties.
[0044] Furthermore, according to the present invention, it is possible to provide a positive electrode for a non-aqueous secondary battery having a positive electrode composite material layer capable of exhibiting excellent adhesiveness and water-removing properties.
[0045] Furthermore, according to the present invention, a nonaqueous secondary battery having the nonaqueous secondary battery positive electrode can be provided. DETAILED DESCRIPTION
[0046] Hereinafter, embodiments of the present invention will be described in detail.
[0047] Here, the non-aqueous secondary battery positive electrode slurry composition of the present invention (hereinafter sometimes referred to as "slurry composition") can be used to form an electrode composite material layer possessed by an electrode (non-aqueous secondary battery electrode) of a non-aqueous secondary battery such as a lithium ion secondary battery. In addition, the non-aqueous secondary battery of the present invention (hereinafter sometimes referred to as "secondary battery") is characterized in that a non-aqueous secondary battery positive electrode (hereinafter sometimes referred to as "positive electrode") having a positive electrode composite material layer formed by the non-aqueous secondary battery positive electrode slurry composition of the present invention is used.
[0048] (Slurry composition for non-aqueous secondary battery electrodes)
[0049] The slurry composition of the present invention is characterized in that it comprises: olivine-type lithium iron phosphate particles (hereinafter sometimes referred to as "olivine-type LFP particles"), at least a portion of the surface of which is coated with a carbon coating and the content of weakly acidic groups on the surface is within a specified range; and a polymer X having a content ratio of acidic group-containing monomer units within a specified range. Moreover, the slurry composition of the present invention has excellent dispersibility. Therefore, if the slurry composition of the present invention is used, a positive electrode composite material layer having a uniform structure can be formed. In addition, the slurry composition of the present invention enables the positive electrode composite material layer formed using the slurry composition to exert excellent adhesion and water removal properties. In this way, the positive electrode composite material layer formed using the slurry composition of the present invention has a uniform structure, and at the same time, the adhesion and water removal properties are also excellent, so the internal resistance of the secondary battery manufactured using the positive electrode having the positive electrode composite material layer can be reduced.
[0050] Furthermore, the slurry composition of the present invention may contain, in addition to the carbon coating layer-covered olivine-type LFP particles and the polymer X, a particulate polymer Y and a conductive material.
[0051] In addition, the slurry composition of the present invention generally further contains a dispersion medium such as water. That is, the slurry composition of the present invention is generally a slurry composition in which the carbon coating-coated olivine-type LFP particles and components such as polymer X are dispersed or dissolved in a dispersion medium such as water.
[0052] Furthermore, the slurry composition of the present invention may further contain components other than the above-mentioned carbon coating layer-covered olivine-type LFP particles, polymer X, particulate polymer Y, conductive material, and dispersion medium.
[0053] <Carbon-coated olivine-type LFP particles>
[0054] The carbon coating-coated olivine-type LFP particles are a material that can function as a positive electrode active material for a secondary battery.
[0055] The carbon coating-coated olivine LFP particles are particles in which at least a portion of the surface of the olivine lithium iron phosphate (LiFePO4) particles is coated with a carbon coating. Here, in the carbon coating-coated olivine LFP particles, the entire surface of the olivine LFP particles may be coated with the carbon coating, or only a portion of the olivine LFP particles may be coated with the carbon coating. In addition, the carbon coating that coats at least a portion of the LFP particles is a layer composed of carbon, which is not particularly limited, for example, it may be a layer composed of amorphous carbon, a layer composed of crystalline carbon, or a layer composed of a mixture of amorphous carbon and crystalline carbon.
[0056] The carbon coating-coated olivine LFP particles can be produced by forming a carbon coating on the surface of the olivine LFP particles.
[0057] As a method for forming a carbon coating, for example, the following well-known methods can be appropriately adopted: a gas phase method such as a CVD (Chemical Vapor Deposition) method in which a gas phase coating raw material is evaporated onto the surface of olivine-type LFP particles in an inert gas atmosphere; a liquid phase method in which a solution obtained by diluting the coating raw material with an appropriate solvent is mixed with olivine-type LFP particles, and the coating raw material is sintered and carbonized in an inert gas atmosphere; a solid phase method in which olivine-type LFP particles and the coating raw material are kneaded without using a solvent and the mixture is sintered and carbonized in an inert gas atmosphere, etc.
[0058] As a coating raw material for the CVD method, a compound (gas) that can be decomposed by heat, plasma, etc. and form a carbon coating on the surface of the above-mentioned olivine-type LFP particles can be used. Examples of the compound include: unsaturated aliphatic hydrocarbons such as ethylene, acetylene, and propylene; saturated aliphatic hydrocarbons such as methane, ethane, and propane; various hydrocarbon compounds such as aromatic hydrocarbons such as benzene, toluene, and naphthalene. These compounds can be used alone or as a mixed gas containing two or more of these compounds in any ratio. The temperature, pressure, time and other conditions in the CVD method can be appropriately selected according to the type of coating raw material used and the desired coating amount.
[0059] As the coating raw material of the liquid phase method, a compound that is soluble in various solvents and can be thermally decomposed to form a carbon coating on the surface of the above-mentioned olivine-type LFP particles can be used. As a preferred example of the compound, asphalts such as coal tar pitch, petroleum pitch, and wood tar pitch can be cited. These can be used alone or in combination of two or more in any ratio. The temperature and time of calcination in the liquid phase method can be appropriately selected according to the type of coating raw material, etc. Calcination in the liquid phase method can be performed at, for example, 800 to 1600°C for 2 to 3 hours.
[0060] As the coating material of the solid phase method, one or more coating materials similar to those of the liquid phase method can be used. The temperature and time of the calcination in the solid phase method can be appropriately selected according to the type of the coating material, and can be within the same range as that of the calcination in the liquid phase method, for example.
[0061] Furthermore, when any of the above methods is used as a method for forming a carbon coating layer, various additives (for example, additives effective for amorphous carbonization of the coating raw material) may be blended into the coating raw material as required.
[0062] Furthermore, commercially available products can also be used as carbon coating-coated olivine-type LFP particles.
[0063] <<Content of weakly acidic groups on the surface>>
[0064] The content of weakly acidic groups on the surface of the carbon coating-coated olivine-type LFP particles needs to be 5 μmol / g or more, preferably 6.5 μmol / g or more, more preferably 8.0 μmol / g or more, and further preferably 10 μmol / g or more, and needs to be 15 μmol / g or less, preferably 13.5 μmol / g or less, and more preferably 12.0 μmol / g or less. If the content of weakly acidic groups on the surface of the carbon coating-coated olivine-type LFP particles is above the above lower limit, it is inferred that the interaction with polymer X increases, so the dispersibility of the slurry composition can be fully improved. On the other hand, if the content of weakly acidic groups on the surface of the carbon coating-coated olivine-type LFP particles is below the above upper limit, the dehydration of the formed positive electrode composite material layer can be fully improved. Thus, by suppressing the generation of gas inside the battery cell of the secondary battery, the electrode reaction can be homogenized, so the internal resistance of the secondary battery can be reduced. Furthermore, when the content of the weakly acidic groups on the surfaces of the carbon coating layer-coated olivine-type LFP particles is equal to or less than the upper limit, aggregation of the particles is suppressed, and thus the dispersibility of the slurry composition can be sufficiently improved.
[0065] In addition, the content of weakly acidic groups on the surface of the carbon-coated olivine LFP particles can be controlled by the above-mentioned method for forming the carbon coating and the treatment after the carbon coating is formed. For example, in the case of adjusting the content of weakly acidic groups on the surface of the obtained carbon-coated olivine LFP particles after the carbon coating is formed on the surface of the olivine LFP particles, the following treatment can be performed. That is, by sintering the carbon-coated olivine LFP particles at a temperature of more than 600°C and less than 800°C in a nitrogen atmosphere, the content of weakly acidic groups on the surface of the carbon-coated olivine LFP particles can be reduced. In addition, by sintering the carbon-coated olivine LFP particles at a temperature of more than 300°C and less than 500°C in an oxygen atmosphere, the content of weakly acidic groups on the surface of the carbon-coated olivine LFP particles can be increased.
[0066] The weakly acidic group present on the surface of the carbon coating layer-coated olivine-type LFP particles is not particularly limited, and examples thereof include a phenolic hydroxyl group (phenolic hydroxyl group) and the like.
[0067] <<G / D ratio of carbon coating>>
[0068] The G / D ratio of the carbon coating of the carbon coating coated olivine LFP particles is preferably 0.4 or more, more preferably 0.60 or more, further preferably 0.670 or more, further preferably 0.690 or more, preferably 0.770 or less, more preferably 0.740 or less, and further preferably 0.710 or less. If the G / D ratio of the carbon coating of the carbon coating coated olivine LFP particles is above the above lower limit, the carbon coating has few defects, so the electronic conductivity of the carbon coating is improved, and thus the internal resistance of the secondary battery can be reduced. On the other hand, if the G / D ratio of the carbon coating of the carbon coating coated olivine LFP particles is below the above upper limit, it is presumed that there will be moderate defects on the carbon coating, thereby improving the hydrophilicity of the carbon coating, and further increasing the interaction with the polymer X, so that the dispersibility of the slurry composition can be further improved.
[0069] <<Average particle size>>
[0070] The particle size of the carbon-coated olivine LFP particles is not particularly limited and can be appropriately adjusted within the range that can achieve the desired effect of the present invention. For example, the average particle size of the carbon-coated olivine LFP particles is preferably greater than 0.1 μm and less than 5 μm, and particularly preferably greater than 0.5 μm and less than 2 μm.
[0071] In the present invention, the "average particle size" of the carbon coating-coated olivine LFP particles refers to the particle size D50 at which the cumulative volume calculated from the small particle size side in the particle size distribution (volume basis) measured by a laser diffraction particle size measuring device manufactured by Malvern Corporation becomes 50%.
[0072] <Polymer X>
[0073] The polymer X is a component that can function as a dispersant in the slurry composition for dispersing components such as the positive electrode active material and the conductive material well. In addition, the polymer X can also function as a binder in the positive electrode composite material layer formed using the slurry composition.
[0074] The polymer X contains the acidic group-containing monomeric unit at a predetermined content ratio. In addition, the polymer X may contain a hydroxyl-containing acrylate monomeric unit in addition to the acidic group-containing monomeric unit. Furthermore, the polymer X may contain monomeric units other than the acidic group-containing monomeric unit and the hydroxyl-containing acrylate monomeric unit (hereinafter sometimes referred to as "other monomeric units").
[0075] In addition, the polymer X is not particularly limited, and is usually a water-soluble polymer. In the present invention, the polymer is "water-soluble" when 0.5 g (solid content conversion) of the polymer is dissolved in 100 g of water at a temperature of 25°C, and the amount of insoluble components is less than 5.0% by mass.
[0076] <<Acidic group-containing monomer unit>>
[0077] Examples of the acidic group-containing monomer capable of forming the acidic group-containing monomer unit in the polymer X include carboxylic acid group-containing monomers, sulfonic acid group-containing monomers, and phosphoric acid group-containing monomers.
[0078] Examples of the carboxylic acid group-containing monomer include monocarboxylic acids and derivatives thereof, dicarboxylic acids and anhydrides thereof, and derivatives thereof.
[0079] Examples of the monocarboxylic acid include acrylic acid, methacrylic acid, and crotonic acid.
[0080] Examples of the monocarboxylic acid derivative include 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, α-chloro-β-E-methoxyacrylic acid, and β-diaminoacrylic acid.
[0081] Examples of the dicarboxylic acid include maleic acid, fumaric acid, and itaconic acid.
[0082] Examples of the dicarboxylic acid derivatives include maleic acid esters such as methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, methylallyl maleate, diphenyl maleate, nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate.
[0083] Examples of the anhydride of dicarboxylic acid include maleic anhydride, acrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride.
[0084] Furthermore, as the monomer having a carboxylic acid group, an acid anhydride that generates a carboxyl group by hydrolysis can also be used.
[0085] In addition, monoesters and diesters of α,β-ethylenically unsaturated polycarboxylic acids such as monoethyl maleate, diethyl maleate, monobutyl maleate, dibutyl maleate, monoethyl fumarate, diethyl fumarate, monobutyl fumarate, dibutyl fumarate, monocyclohexyl fumarate, dicyclohexyl fumarate, monoethyl itaconate, diethyl itaconate, monobutyl itaconate, and dibutyl itaconate can also be mentioned.
[0086] In addition, the carboxylic acid group in the carboxylic acid group-containing monomer may be in the form of an inorganic salt or an organic salt in which the hydrogen atom is replaced by an inorganic ion or an organic ion. That is, the carboxylic acid group-containing monomer may be in the form of a carboxylate salt.
[0087] Examples of the sulfonic acid group-containing monomer include vinyl sulfonic acid, methylvinyl sulfonic acid, (meth)allyl sulfonic acid, styrene sulfonic acid, ethyl (meth)acrylate-2-sulfonate, 2-acrylamide-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid.
[0088] In addition, the hydrogen atom in the sulfonic acid group in the sulfonic acid group-containing monomer may be replaced by an inorganic ion or an organic ion to form an inorganic salt or an organic salt. That is, the sulfonic acid group-containing monomer may be in the form of a sulfonate.
[0089] Examples of the phosphoric acid group-containing monomer include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate.
[0090] In addition, the phosphoric acid group in the phosphoric acid group-containing monomer may be in the form of an inorganic salt or an organic salt in which the hydrogen atom is replaced by an inorganic ion or an organic ion. That is, the phosphoric acid group-containing monomer may be in the form of a phosphate.
[0091] In addition, these acidic group-containing monomers may be used alone or in combination of two or more at any ratio.
[0092] Furthermore, from the viewpoint of further improving the adhesiveness of the formed positive electrode composite material layer, it is preferable to use a carboxylic acid group-containing monomer or a sulfonic acid group-containing monomer as the acidic group-containing monomer.
[0093] The proportion of the acidic group-containing monomeric unit in polymer X, when all monomeric units contained in polymer X are taken as 100% by mass, needs to be 3% by mass or more, preferably 4% by mass or more, more preferably 4.5% by mass or more, further preferably 5% by mass or more, further preferably 6% by mass or more, and further preferably 8% by mass or more, needs to be 40% by mass or less, preferably 35% by mass or less, and more preferably 30% by mass or less. If the proportion of the acidic group-containing monomeric unit in polymer X is 3% by mass or more, it is inferred that the interaction with the carbon coating coated olivine LFP particles increases, so the dispersibility of the slurry composition can be fully improved. In addition, if the proportion of the acidic group-containing monomeric unit in polymer X is 3% by mass or more, the adhesion of the positive electrode composite material layer formed can be fully improved. Furthermore, if the proportion of the acidic group-containing monomeric unit in polymer X is 3% by mass or more, it is inferred that the interaction with the carbon coating coated olivine LFP particles increases, so the dehydration of the positive electrode composite material layer formed can be fully improved. On the other hand, if the content of the acidic group-containing monomer unit in the polymer X is 40% by mass or less, it is estimated that the flexibility of the polymer X is increased, so the flexibility of the formed positive electrode composite material layer can be sufficiently ensured and the adhesiveness of the positive electrode composite material layer can be sufficiently improved.
[0094] <<Hydroxy-containing acrylate monomer unit>>
[0095] Examples of the hydroxyl-containing acrylate monomers that can form the hydroxyl-containing acrylate monomer units in the polymer X include alkyl esters of acrylic acid such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, and 4-hydroxybutyl acrylate (also referred to as "hydroxyalkyl acrylate monomers"); general formula: CH2=CH-COO-(C q H 2q O) p -H (wherein p is an integer of 2 to 9, and q is an integer of 2 to 4) and esters of acrylic acid (also referred to as "polyalkylene glycol acrylate monomers"), etc. These may be used alone or in any combination.
[0096] Among them, from the viewpoint of further improving the adhesion of the positive electrode composite material layer, as the hydroxyl-containing acrylate monomer, alkyl esters of acrylic acid (hydroxyalkyl acrylate monomers) such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, and 4-hydroxybutyl acrylate are preferably used.
[0097] The content ratio of the hydroxyl-containing acrylate monomer unit in the polymer X is preferably 55% by mass or more, more preferably 57.5% by mass or more, more preferably 60% by mass or more, more preferably 70% by mass or more, preferably 90% by mass or less, more preferably 85% by mass or less, and more preferably 80% by mass or more. If the content ratio of the hydroxyl-containing acrylate monomer unit in the polymer X is above the lower limit, it is inferred that the flexibility of the polymer X increases, so the flexibility of the positive electrode composite material layer formed can be fully ensured, and the adhesion of the positive electrode composite material layer can be further improved. On the other hand, if the content ratio of the hydroxyl-containing acrylate monomer unit in the polymer X is below the upper limit, it is inferred that the flexibility of the polymer X can be suppressed from being excessively increased, so the adhesion of the positive electrode composite material layer formed can be fully ensured.
[0098] <<Other monomer units>>
[0099] The polymer X may also contain other monomer units.
[0100] The other monomer units in the polymer X are not particularly limited as long as the desired effects of the present invention can be obtained, and examples thereof include hydroxyl group-containing methacrylate monomer units, unsaturated carboxylic acid amide monomer units, and nitrile group-containing monomer units.
[0101] [Hydroxy-containing methacrylate monomer unit]
[0102] Examples of the hydroxyl-containing methacrylate monomers that can form the hydroxyl-containing methacrylate monomer units in the polymer X include methacrylic acid alkyl esters such as 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate (also referred to as "methacrylic acid hydroxyalkyl ester monomers"); general formula: CH2=C(CH3)-COO-(C s H 2s O) r -H (wherein r represents an integer of 2 to 9, and s represents an integer of 2 to 4) and esters of methacrylic acid (also referred to as "methacrylic acid polyalkylene glycol ester monomer"), etc. These may be used alone or in combination of two or more at any ratio.
[0103] Among them, from the viewpoint of further improving the adhesiveness of the positive electrode mixture layer, methacrylic acid alkanol esters (hydroxyalkyl methacrylate monomers) such as 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate are preferably used as the hydroxyl group-containing methacrylate monomer.
[0104] The content ratio of the hydroxyl-containing methacrylate monomer unit in the polymer X is preferably 5% by mass or more, more preferably 7.5% by mass or more, more preferably 10% by mass or more, preferably 30% by mass or less, more preferably 27.5% by mass or less, and more preferably 25% by mass or less, when all monomer units contained in the polymer X are taken as 100% by mass. If the content ratio of the hydroxyl-containing methacrylate monomer unit in the polymer X is within the above-defined range, the softness of the formed positive electrode composite material layer can be improved, and the adhesion of the positive electrode composite material layer can be further improved.
[0105] The total content ratio of the hydroxyl-containing acrylate monomer units and the hydroxyl-containing methacrylate monomer units in the polymer X is preferably 60% by mass or more, more preferably 70% by mass or more, more preferably 80% by mass or more, preferably 97% by mass or less, more preferably 95.5% by mass or less, and more preferably 94% by mass or less. If the total content ratio of the hydroxyl-containing acrylate monomer units and the hydroxyl-containing methacrylate monomer units in the polymer X is above the above lower limit, the softness of the formed positive electrode composite material layer can be improved, and the adhesion of the positive electrode composite material layer can be further improved. On the other hand, if the total content ratio of the hydroxyl-containing acrylate monomer units and the hydroxyl-containing methacrylate monomer units in the polymer X is below the above upper limit, the content ratio of the above-mentioned acidic group-containing monomer units can be fully ensured, so the dispersibility of the slurry composition and the adhesion of the formed positive electrode composite material layer can be fully ensured.
[0106] [Unsaturated carboxylic acid amide monomer unit]
[0107] As an unsaturated carboxylic acid amide monomer capable of forming an unsaturated carboxylic acid amide monomer unit, a compound having a chemical structure formed by dehydration condensation of an unsaturated carboxylic acid such as (meth) acrylic acid and ammonia, a primary amine or a secondary amine can be used. As a specific example of an unsaturated carboxylic acid amide monomer, acrylamide, methacrylamide, N,N- dimethylacrylamide, N,N- dimethylmethacrylamide, N-isopropylacrylamide, N-isobutylacrylamide, etc. can be cited. These can be used alone or in any ratio. Two or more can be used. Among them, from the viewpoint of improving the intermolecular interaction caused by the hydrogen bonds in the polymer X and further improving the adhesion of the positive electrode composite material layer formed, acrylamide and methacrylamide are preferably used, and acrylamide is more preferably used.
[0108] The content of the unsaturated carboxylic acid amide monomer units in the polymer X may be 0% by mass or more, preferably 1% by mass or more, preferably 2% by mass or more, and preferably 20% by mass or less, when all monomer units contained in the polymer X are taken as 100% by mass.
[0109] The content ratio of the unsaturated carboxylic acid amide monomer units in the polymer X may be 10% by mass or less, or 5% by mass or less, when all monomer units contained in the polymer X are taken as 100% by mass.
[0110] Furthermore, of course, the polymer X may not contain the unsaturated carboxylic acid amide monomer unit.
[0111] [Nitrile-containing monomer unit]
[0112] As the nitrile-containing monomer capable of forming the nitrile-containing monomer unit, α,β-ethylenically unsaturated nitrile monomers can be cited. Moreover, as the α,β-ethylenically unsaturated nitrile monomer, there is no particular limitation as long as it is an α,β-ethylenically unsaturated compound having a nitrile group, and examples thereof include: acrylonitrile; α-halogenated acrylonitrile such as α-chloroacrylonitrile and α-bromoacrylonitrile; α-alkyl acrylonitrile such as methacrylonitrile and α-ethylacrylonitrile, etc. Among these, as the nitrile-containing monomer, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred.
[0113] These may be used alone or in combination of two or more at any ratio.
[0114] The content ratio of the nitrile group-containing monomer unit in the polymer X can be 0 mass % or more, preferably 1 mass % or more, preferably 2 mass % or more, preferably 10 mass % or less, preferably 5 mass % or less, when all monomer units contained in the polymer X are taken as 100 mass %.
[0115] The content of the nitrile group-containing monomer units in the polymer X may be 2% by mass or less, or 1% by mass or less, when all monomer units contained in the polymer X are taken as 100% by mass.
[0116] In addition, of course, the polymer X may not contain the nitrile group-containing monomer unit.
[0117] <<Method for preparing polymer X>>
[0118] The polymer X is not particularly limited and can be prepared, for example, as follows.
[0119] In a solvent such as water, the above-mentioned acidic group-containing monomer, hydroxyl-containing acrylate monomer and other monomers are mixed. A polymerization accelerator is added to the obtained mixture. Afterwards, a polymerization initiator is added to initiate a polymerization reaction. Afterwards, as required, one or more cycles of adding a polymerization accelerator, adding a polymerization initiator and polymerization can be performed. When a polymerization initiator is added to initiate a polymerization reaction, the polymerization temperature is preferably, for example, above 35°C and below 65°C, more preferably above 40°C and below 55°C. In addition, the time of the polymerization reaction between the addition of a polymerization initiator and the addition of a polymerization accelerator is, for example, preferably above 5 minutes and below 40 minutes, more preferably above 10 minutes and below 30 minutes. In addition, the above operation is preferably carried out under a nitrogen atmosphere. In addition, a chain transfer agent can also be used as a polymerization aid when performing a polymerization reaction. After the polymerization reaction, a reaction terminator is used to terminate the polymerization reaction. Next, the product is cooled, placed in an air atmosphere, and then a lithium hydroxide aqueous solution is added to adjust the pH of the product to above 7.0 and below 9.0.
[0120] The polymerization initiator is not particularly limited, and known polymerization initiators can be used. Examples of the polymerization initiator include potassium persulfate, sodium persulfate, ammonium persulfate, etc. Potassium persulfate is particularly preferred. When the polymerization initiator is added multiple times, the polymerization initiators each time may be the same or different.
[0121] The amount of the polymerization initiator used can be appropriately adjusted within a range in which the desired effects of the present invention can be obtained.
[0122] As the polymerization accelerator, for example, L-ascorbic acid, sodium bisulfite, etc. can be mentioned. In the case of adding the polymerization accelerator multiple times, the polymerization accelerators each time may be the same or different. In particular, when initiating the polymerization reaction, it is preferred that L-ascorbic acid is present as the polymerization accelerator in the polymerization system.
[0123] The amount of the polymerization accelerator used can be appropriately adjusted within a range in which the desired effects of the present invention can be obtained.
[0124] <<Weight average molecular weight (Mw)>>
[0125] The weight average molecular weight (Mw) of polymer X is preferably 50,000 or more, more preferably 75,000 or more, further preferably 100,000 or more, further preferably 150,000 or more, preferably less than 500,000, more preferably less than 400,000, further preferably less than 300,000. If the weight average molecular weight (Mw) of polymer X is above the lower limit, the adhesion of the formed positive electrode composite material layer can be further improved; on the other hand, if the weight average molecular weight (Mw) of polymer X is less than the upper limit, the dispersibility of the slurry composition can be further improved.
[0126] The weight average molecular weight (Mw) of the polymer X can be controlled by the polymerization conditions in the method for preparing the polymer X, specifically, by the type and amount of polymerization initiator, polymerization accelerator, chain transfer agent, etc., and the time and temperature of the polymerization reaction.
[0127] <<Molecular weight distribution (Mw / Mn)>>
[0128] The molecular weight distribution (Mw / Mn) of the polymer X is preferably 1.5 or more, more preferably 1.8 or more, further preferably 2.2 or more, further preferably 3 or more, and is preferably 10 or less, more preferably 7 or less, further preferably 4 or less.
[0129] The molecular weight distribution (Mw / Mn) of polymer X can be controlled by the polymerization conditions in the method for preparing polymer X, specifically, by the type and amount of polymerization initiator, polymerization accelerator, chain transfer agent, etc., and the time and temperature of the polymerization reaction.
[0130] <<Content in slurry composition>>
[0131] The content of polymer X in the slurry composition can be appropriately adjusted within the range of the desired effect of the present invention, for example, relative to 100 parts by mass of carbon coating coated olivine type LFP particles, preferably 0.1 parts by mass or more and 5 parts by mass or less. If the content of polymer X in the slurry composition is above the above lower limit, the dispersibility of the slurry composition and the adhesion of the positive electrode composite material layer formed can be further improved. On the other hand, if the content of polymer X in the slurry composition is below the above upper limit, the internal resistance of the secondary battery can be reduced.
[0132] <Granular polymer Y>
[0133] The particulate polymer Y is a component that can function as a binder in the positive electrode composite material layer together with the polymer X.
[0134] In addition, the particulate polymer Y is a polymer different from the polymer X described above.
[0135] Furthermore, the particulate polymer Y preferably contains a hydrophilic group. When a particulate polymer containing a hydrophilic group is used as the particulate polymer Y, the dispersibility of the slurry composition and the adhesiveness of the formed positive electrode composite material layer can be further improved.
[0136] Here, the method for introducing the hydrophilic group into the particulate polymer Y is not particularly limited, and for example, a method in which a hydrophilic group-containing monomer is used when polymerizing the particulate polymer Y to form a hydrophilic group-containing monomer unit in the obtained particulate polymer Y can be used.
[0137] <<Hydrophilic group-containing monomer unit>>
[0138] Examples of the hydrophilic group-containing monomer capable of forming the hydrophilic group-containing monomer unit in the particulate polymer Y include acidic group-containing monomers such as carboxylic acid group-containing monomers, sulfonic acid group-containing monomers and phosphoric acid group-containing monomers, and hydroxyl group-containing monomers.
[0139] As the acidic group-containing monomer (a carboxylic acid group-containing monomer, a sulfonic acid group-containing monomer, a phosphoric acid group-containing monomer, etc.), various acidic group-containing monomers that can be used for preparing the above-mentioned polymer X can be used.
[0140] Examples of hydroxyl-containing monomers include alkyl alcohol esters of ethylenically unsaturated carboxylic acids such as 2-hydroxyethyl acrylate (2-hydroxyethyl acrylate), 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, di-2-hydroxyethyl maleate, di-4-hydroxybutyl maleate, and di-2-hydroxypropyl itaconate; general formula: CH2=CR 1 -COO-(C q H 2q O) p -H (wherein p represents an integer of 2 to 9, q represents an integer of 2 to 4, R 1Esters of polyalkylene glycol represented by alkylene glycol (representing hydrogen or methyl) and (meth)acrylic acid; mono(meth)acrylates of dihydroxy esters of dicarboxylic acids such as 2-hydroxyethyl-2'-(meth)acryloyloxyphthalate and 2-hydroxyethyl-2'-(meth)acryloyloxysuccinate; vinyl ethers such as 2-hydroxyethyl vinyl ether and 2-hydroxypropyl vinyl ether; (meth)allyl-2-hydroxyethyl ether, (meth)allyl-2-hydroxypropyl ether, (meth)allyl-3-hydroxypropyl ether, (meth)allyl-2-hydroxybutyl ether, (meth)allyl-3-hydroxybutyl ether, (meth)allyl-4-hydroxybutyl ether, (meth)allyl- Mono(meth)allyl ethers of alkylene glycols such as 6-hydroxyhexyl ether; mono(meth)allyl ethers of polyoxyalkylene glycols such as diethylene glycol mono(meth)allyl ether and dipropylene glycol mono(meth)allyl ether; mono(meth)allyl ethers of halides and hydroxyl-substituted (poly)alkylene glycols such as glycerol mono(meth)allyl ether, (meth)allyl-2-chloro-3-hydroxypropyl ether and (meth)allyl-2-hydroxy-3-chloropropyl ether; mono(meth)allyl ethers of polyphenols such as eugenol and isoeugenol and their halides; (meth)allyl sulfides of alkylene glycols such as (meth)allyl-2-hydroxyethyl sulfide and (meth)allyl-2-hydroxypropyl sulfide, etc.
[0141] In the present invention, "(meth)allyl" means an allyl group and / or a methallyl group, and "(meth)acryloyl" means an acryloyl group and / or a methacryloyl group.
[0142] As the hydrophilic group-containing monomer, one kind may be used alone, or two or more kinds may be used in combination at any ratio.
[0143] Moreover, as the hydrophilic group-containing monomer, from the viewpoint of further improving the dispersibility of the slurry composition and the adhesion of the formed positive electrode composite material layer, it is preferred to use an acidic group-containing monomer (a carboxylic acid group-containing monomer, a sulfonic acid group-containing monomer, and a phosphoric acid group-containing monomer, etc.), and from the viewpoint of further improving the adhesion of the formed positive electrode composite material layer, it is preferred to use an acidic group-containing monomer and a hydroxyl group-containing monomer in combination, and it is further preferred to use a carboxylic acid group-containing monomer and a hydroxyl group-containing monomer in combination.
[0144] -Content ratio-
[0145] The content ratio of the hydrophilic group-containing monomer unit in the granular polymer Y is preferably 1% by mass or more and 10% by mass or less, based on 100% by mass of all monomer units contained in the granular polymer Y. If the content ratio of the hydrophilic group-containing monomer unit in the granular polymer Y is within the above-specified range, the dispersibility of the slurry composition and the adhesion of the formed positive electrode composite material layer can be further improved.
[0146] Furthermore, in the case where the granular polymer Y includes both an acidic group-containing monomer unit (a carboxylic acid-containing monomer unit, a sulfonic acid-containing monomer unit, and a phosphoric acid-containing monomer unit, etc.) and a hydroxyl-containing monomer unit as a hydrophilic group-containing monomer unit, the content ratio of the hydrophilic group-containing monomer unit in the granular polymer Y (i.e., the total content ratio of the acidic group-containing monomer unit and the hydroxyl-containing monomer unit) is more preferably 2% by mass or more, more preferably 3% by mass or more, more preferably 5% by mass or less, and more preferably 4% by mass or less, when all monomer units contained in the granular polymer Y are taken as 100% by mass. If the total content ratio of the acidic group-containing monomer unit and the hydroxyl-containing monomer unit in the granular polymer Y is within the above-specified range, the dispersibility of the slurry composition and the adhesion of the formed positive electrode composite material layer can be further improved.
[0147] In addition, in the case where the granular polymer Y includes an acidic group-containing monomer unit (a carboxylic acid group-containing monomer unit, a sulfonic acid group-containing monomer unit, and a phosphoric acid group-containing monomer unit, etc.) as a hydrophilic group-containing monomer unit, the content ratio of the acidic group-containing monomer unit in the granular polymer Y is preferably 0.5% by mass or more, more preferably 1% by mass or more, more preferably 1.5% by mass or more, preferably 5% by mass or less, more preferably 3% by mass or less, and more preferably 2.5% by mass or less. If the content ratio of the acidic group-containing monomer unit in the granular polymer Y is above the above lower limit, the dispersibility of the slurry composition and the adhesion of the positive electrode composite material layer formed can be further improved. On the other hand, if the content ratio of the acidic group-containing monomer unit in the granular polymer Y is below the above upper limit, the softness of the positive electrode composite material layer formed can be fully ensured.
[0148] In addition, in the case where the granular polymer Y includes a hydroxyl-containing monomer unit as a hydrophilic group-containing monomer unit, the content ratio of the hydroxyl-containing monomer unit in the granular polymer Y is preferably 0.5% by mass or more, more preferably 1% by mass or more, preferably 5% by mass or less, more preferably 2% by mass or less, and further preferably 1.5% by mass or less, when all monomer units contained in the granular polymer Y are taken as 100% by mass. If the content ratio of the acidic group-containing monomer unit in the granular polymer Y is above the above lower limit, the softness of the positive electrode composite material layer formed can be improved. On the other hand, if the content ratio of the acidic group-containing monomer unit in the granular polymer Y is below the above upper limit, the dispersibility of the slurry composition and the adhesion of the positive electrode composite material layer formed can be fully ensured.
[0149] <<Type of granular polymer Y>>
[0150] Moreover, as the particulate polymer Y containing a hydrophilic group, for example, a hydrophilic group-containing acrylic polymer or a hydrophilic group-containing conjugated diene polymer is preferably used. From the viewpoint of sufficiently ensuring the cycle characteristics of the secondary battery, a hydrophilic group-containing acrylic polymer is more preferably used.
[0151] -Acrylic polymer containing hydrophilic groups-
[0152] The hydrophilic group-containing acrylic polymer is a copolymer that contains at least a (meth) acrylic acid ester monomer unit in addition to the above-mentioned hydrophilic group-containing monomer unit. In addition, the hydrophilic group-containing acrylic polymer preferably also contains a nitrile-containing monomer unit. In addition, the hydrophilic group-containing acrylic polymer may also contain monomer units other than the hydrophilic group-containing monomer unit, the (meth) acrylic acid ester monomer unit and the nitrile-containing monomer unit.
[0153] The content ratio of the hydrophilic group-containing monomeric unit in the hydrophilic group-containing acrylic polymer can be in the same range as the preferred range of the content ratio of the hydrophilic group-containing monomeric unit in the above-mentioned polymer.
[0154] As the (meth)acrylate monomer that can form the (meth)acrylate monomer unit in the hydrophilic group-containing acrylic polymer, alkyl (meth)acrylates such as methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, and 2-ethylhexyl acrylate can be used. In addition, these can be used alone or in any ratio.
[0155] In addition, in this specification, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.
[0156] Here, the content ratio of the (meth) acrylic acid ester monomer unit in the hydrophilic group-containing acrylic acid polymer is preferably 50% by mass or more, more preferably 60% by mass or more, more preferably 70% by mass or more, preferably 90% by mass or less, more preferably 85% by mass or less, and more preferably 80% by mass or less. If the content ratio of the (meth) acrylic acid ester monomer unit in the hydrophilic group-containing acrylic acid polymer is within the above-mentioned specified range, the adhesion of the positive electrode composite material layer formed can be further improved.
[0157] As the nitrile group-containing monomer capable of forming the nitrile group-containing monomer unit in the hydrophilic group-containing acrylic polymer, the nitrile group-containing monomer capable of forming the above-mentioned polymer X can be used.
[0158] The proportion of the nitrile-containing monomeric unit in the hydrophilic group-containing acrylic polymer is preferably 5% by mass or more, more preferably 10% by mass or more, more preferably 17% by mass or more, preferably 40% by mass or less, more preferably 35% by mass or less, and more preferably 26% by mass or less, when all monomeric units contained in the hydrophilic group-containing acrylic polymer are taken as 100% by mass. If the proportion of the nitrile-containing monomeric unit in the hydrophilic group-containing acrylic polymer is within the above-mentioned prescribed range, the adhesion of the positive electrode composite material layer formed can be further improved.
[0159] -Hydrophilic group-containing conjugated diene polymer-
[0160] The hydrophilic group-containing conjugated diene polymer is a copolymer containing a conjugated diene monomer unit in addition to the above-mentioned hydrophilic group-containing monomer unit.
[0161] As specific examples of conjugated diene polymers, there are no particular limitations, and examples include: copolymers containing hydrophilic group-containing styrene-butadiene copolymers (containing hydrophilic groups SBR) and the like, containing hydrophilic group-containing monomer units, aromatic vinyl monomer units and aliphatic conjugated diene monomer units; butadiene rubber containing hydrophilic groups (containing hydrophilic groups BR) (comprising copolymers containing hydrophilic group-containing monomer units and butadiene units); acrylic rubber containing hydrophilic groups (containing hydrophilic groups NBR) (comprising copolymers containing hydrophilic group-containing monomer units, acrylonitrile units and butadiene units), and their hydrogenated products, etc. These can be used alone or in any ratio.
[0162] Among them, from the viewpoint of further improving the adhesion of the formed electrode composite material layer, it is preferred to use a copolymer containing a hydrophilic group-containing monomer unit, an aromatic vinyl monomer unit and an aliphatic conjugated diene monomer unit, such as a hydrophilic group-containing styrene-butadiene copolymer (hydrophilic group-containing SBR).
[0163] The content ratio of the hydrophilic group-containing monomeric unit in the hydrophilic group-containing conjugated diene polymer can be in the same range as the preferred range of the content ratio of the hydrophilic group-containing monomeric unit in the above-mentioned polymer.
[0164] As the conjugated diene monomer unit that can form the conjugated diene monomer unit in the conjugated diene polymer containing a hydrophilic group, conjugated diene compounds such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene can be cited. These can be used alone or in any ratio. 1,3-butadiene is particularly preferred.
[0165] The proportion of the conjugated diene monomer unit in the hydrophilic group-containing conjugated diene polymer is preferably 15% by mass or more, more preferably 20% by mass or more, more preferably 25% by mass or more, preferably 60% by mass or less, more preferably 50% by mass or less, and more preferably 40% by mass or less. If the proportion of the conjugated diene monomer unit in the hydrophilic group-containing conjugated diene polymer is within the above-mentioned prescribed range, the adhesion of the positive electrode composite material layer formed can be further improved.
[0166] As aromatic vinyl monomers capable of forming aromatic vinyl monomer units in the hydrophilic group-containing conjugated diene polymer, styrene, α-methylstyrene, vinyltoluene, divinylbenzene, etc. can be mentioned. These can be used alone or in any ratio. Styrene is particularly preferred.
[0167] The proportion of the aromatic vinyl monomer unit in the hydrophilic group-containing conjugated diene polymer is preferably 30% by mass or more, more preferably 45% by mass or more, more preferably 56% by mass or more, preferably 80% by mass or less, more preferably 75% by mass or less, and more preferably 71% by mass or less. If the proportion of the aromatic vinyl monomer unit in the hydrophilic group-containing conjugated diene polymer is within the above-mentioned range, the adhesion of the positive electrode composite material layer formed can be further improved.
[0168] <<Method for preparing granular polymer Y>>
[0169] The polymerization method of the particulate polymer A is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. can be used. In addition, as the polymerization reaction, addition polymerization such as ion polymerization, free radical polymerization, and living free radical polymerization can be used. Moreover, the emulsifier, dispersant, polymerization initiator, chain transfer agent, etc. that can be used for polymerization can use those commonly used, and the amount used can also be the amount commonly used.
[0170] <<Content in slurry composition>>
[0171] The content ratio of the granular polymer Y in the slurry composition can be appropriately adjusted within the range of the desired effect of the present invention, for example, relative to 100 parts by mass of carbon coating coated olivine type LFP particles, preferably 0.5 parts by mass or more, more preferably 0.8 parts by mass or more, preferably 5 parts by mass or less, more preferably 3 parts by mass or less. If the content of the granular polymer Y in the slurry composition is above the above lower limit, the dispersibility of the slurry composition and the adhesion of the positive composite material layer formed can be further improved. On the other hand, if the content of the polymer X in the slurry composition is below the above upper limit, the softness of the positive composite material layer formed can be fully ensured.
[0172] <Conductive materials>
[0173] The conductive material is a component having a function of ensuring electrical contact between the positive electrode active materials (olivine-type LFP particles coated with a carbon coating layer) in the positive electrode composite material layer.
[0174] As the conductive material, for example, at least one of carbon nanotubes and particulate conductive materials can be used. It is preferable to use at least carbon nanotubes, and it is more preferable to use carbon nanotubes and particulate conductive materials in combination.
[0175] If at least carbon nanotubes are used as the conductive material, the internal resistance of the secondary battery can be reduced. Furthermore, if carbon nanotubes and a granular conductive material are used together as the conductive material, the internal resistance of the secondary battery can be reduced and the flexibility of the positive electrode composite material layer can be improved.
[0176] In addition, as the conductive material, conductive materials other than carbon nanotubes and granular conductive materials (other conductive materials) may be used. As other conductive materials, for example, fibrous conductive materials other than carbon nanotubes may be used.
[0177] <<Carbon Nanotube>>
[0178] Carbon nanotubes can reduce the internal resistance of secondary batteries by forming a conductive path in the positive electrode composite material layer. In addition, the use of carbon nanotubes can also improve the cycle characteristics and low-temperature characteristics of secondary batteries.
[0179] The carbon nanotubes are not particularly limited as long as they are carbon nanotubes (hereinafter sometimes referred to as "CNTs") that can achieve the desired effects of the present invention. As carbon nanotubes, single-walled (SW) carbon nanotubes and multi-walled (MW) carbon nanotubes can be cited according to the type of layer form. In addition, the carbon nanotubes that can be used as conductive materials can be any of single-walled carbon nanotubes, multi-walled carbon nanotubes, or a combination thereof.
[0180] The average number of CNT layers is preferably 10 or less, more preferably 9 or less, further preferably 8 or less, further preferably 2 or less, and further preferably 1.5 or less. If the average number of CNT layers is below the upper limit, the cycle characteristics of the secondary battery can be further improved.
[0181] The lower limit of the average number of CNT layers is not particularly limited, but is usually 1 or more.
[0182] The average diameter of CNT is preferably 0.5nm or more, more preferably 1nm or more, more preferably 1.5nm or more, more preferably 2nm or more, more preferably 2.5nm or more, preferably 20nm or less, more preferably 12nm or less, more preferably 8nm or less, more preferably 6nm or less, and more preferably 4nm or less. If the average diameter of CNT is above the lower limit, the agglomeration of CNT can be fully suppressed, and the dispersibility of CNT as a conductive material can be fully ensured. On the other hand, if the average diameter of CNT is below the upper limit, a good conductive path can be formed in the positive electrode composite material layer, the internal resistance of the secondary battery can be further reduced, and the cycle characteristics of the secondary battery can be further improved.
[0183] The ratio of the G band peak intensity of CNT in the Raman spectrum to the D band peak intensity (G / D ratio) is preferably 0.6 or more, more preferably 1.2 or more, further preferably 2.1 or more, further preferably 3.0 or more, and further preferably 3.6 or more. If the G / D ratio of CNT is above the above lower limit, the cycle characteristics of the secondary battery can be further improved. In addition, the upper limit of the G / D ratio of CNT is not particularly limited, for example, 200 or less.
[0184] The BET specific surface area of CNT is preferably 100 m 2 / g or more, more preferably 200m 2 / g or more, more preferably 250m 2 / g or more, preferably 1200m 2 / g or less, more preferably 1100m 2 / g or less, more preferably 1000m 2 When the BET specific surface area of CNT is within the above-specified range, the internal resistance of the secondary battery can be further reduced.
[0185] In the present invention, the "BET specific surface area" of CNT refers to the nitrogen adsorption specific surface area measured using the BET method.
[0186] [Method for producing carbon nanotubes]
[0187] The CNTs having the above-mentioned properties are not particularly limited, and can be produced using known methods such as an arc discharge method, a laser ablation method, and a super growth method.
[0188] [Content in slurry composition]
[0189] The content of CNT in the slurry composition can be appropriately adjusted within the range of the desired effect of the present invention, for example, relative to 100 parts by mass of carbon coating coated olivine type LFP particles, preferably more than 0.01 parts by mass, more preferably more than 0.05 parts by mass, more preferably more than 0.1 parts by mass, preferably less than 2.5 parts by mass, more preferably less than 1.5 parts by mass, more preferably less than 1.0 parts by mass. If the content of CNT in the slurry composition is more than the above lower limit, the internal resistance of the secondary battery can be further reduced. On the other hand, if the content of CNT in the slurry composition is less than the above upper limit, the softness of the positive electrode composite material layer formed can be fully and highly ensured.
[0190] <<Granular conductive material>>
[0191] The particulate conductive material is a component that can function as a conductive material in the positive electrode composite layer and can improve the flexibility of the electrode composite layer.
[0192] The granular conductive material is not particularly limited as long as it has a shape other than a fiber shape (e.g., a spherical shape, a plate shape, etc.), and examples thereof include carbon black (e.g., acetylene black, Ketjen black (registered trademark), furnace black, etc.) and graphene, etc. In addition, these granular conductive materials may be used alone or in combination of two or more in any ratio.
[0193] [Content in slurry composition]
[0194] The content of the granular conductive material in the slurry composition can be appropriately adjusted within the range of the desired effect of the present invention, for example, relative to 100 parts by mass of carbon coating coated olivine type LFP particles, preferably more than 0.1 parts by mass, more preferably more than 0.5 parts by mass, more preferably more than 1 part by mass, preferably less than 5 parts by mass, more preferably less than 3 parts by mass, more preferably less than 2 parts by mass. If the content of the granular conductive material in the slurry composition is more than the above lower limit, the softness of the positive composite material layer formed can be further improved. On the other hand, if the content of the granular conductive material in the slurry composition is less than the above upper limit, the adhesion of the positive composite material layer formed can be fully ensured.
[0195] <<Mixing ratio of CNT and granular conductive material>>
[0196] The mixing ratio of CNT and granular conductive material is not particularly limited. For example, the proportion of CNT content in the total content of CNT and granular conductive material in the slurry composition is preferably 1% by mass or more, more preferably 2% by mass or more, more preferably 3% by mass or more, preferably 30% by mass or less, more preferably 20% by mass or less, and more preferably 10% by mass or less. If the proportion of CNT content in the total content of CNT and granular conductive material is above the above lower limit, the internal resistance of the secondary battery can be further reduced. On the other hand, if the proportion of CNT content in the total content of CNT and granular conductive material is below the above upper limit, the flexibility of the positive electrode composite material layer can be further improved.
[0197] <Dispersion medium>
[0198] The slurry composition of the present invention generally contains a dispersion medium such as water.
[0199] In addition, as at least a part of the dispersion medium of the slurry composition of the present invention, for example, a solvent such as water contained in the binder composition for preparing the slurry composition can be used.
[0200] <Other ingredients>
[0201] In addition, the slurry composition of the present invention may include any other components such as reinforcing materials, leveling agents, viscosity modifiers, electrolyte additives, etc. in addition to the above-mentioned polymer X, granular polymer Y, conductive materials, and dispersion media. These components are not particularly limited as long as they do not affect the battery reaction, and known components can be used. In addition, these components can be used alone or in combination of two or more in any ratio.
[0202] <Method for preparing slurry composition>
[0203] The slurry composition of the present invention is not particularly limited, and can be prepared, for example, by dispersing or dissolving the above-mentioned components in a dispersion medium. Specifically, the slurry composition can be prepared by mixing the above-mentioned components with a dispersion medium using a ball mill, a sand mill, a bead mill, a pigment disperser, an attritor, an ultrasonic disperser, a homogenizer, a planetary mixer, a FILMIX or other mixer.
[0204] Here, water is generally used as the dispersion medium, but an aqueous solution of an arbitrary compound, a mixed solution of a small amount of an organic medium and water, or the like may be used.
[0205] In addition, when preparing the slurry composition of the present invention, when a conductive material such as the above-mentioned CNT and granular conductive material is used, it is also possible to prepare a dispersion in advance in which the conductive material such as the CNT and granular conductive material is dispersed in a dispersion medium such as water, and then mix the obtained dispersion with other components such as the electrode active material, the polymer X and the granular polymer Y.
[0206] (Positive electrode for non-aqueous secondary batteries)
[0207] The positive electrode of the present invention has a positive electrode composite material layer formed using the slurry composition of the present invention, and generally has a structure in which a positive electrode composite material layer is formed on a current collector. Therefore, the positive electrode composite material layer contains at least carbon coating-coated olivine-type LFP particles and polymer X as positive electrode active materials, and optionally further contains particulate polymer Y and conductive materials.
[0208] The components contained in the positive electrode composite material layer, such as the carbon coating-coated olivine LFP particles, polymer X, granular polymer Y and conductive material, are the components contained in the above-mentioned slurry composition, and the preferred content ratio of each component is the same as the preferred content ratio of each component when the total solid content contained in the slurry composition is taken as 100% by mass.
[0209] The preferred ratio of CNT content to the total content of CNT and particulate conductive material that can be contained in the positive electrode composite material layer is also the same as the preferred ratio of CNT content to the total content of CNT and particulate conductive material that can be contained in the slurry composition.
[0210] In addition, the positive electrode of the present invention may further include a conductive adhesive layer containing at least a conductive material and a binder between the current collector and the positive electrode composite material layer.
[0211] Furthermore, since the positive electrode composite material layer included in the electrode of the present invention is formed using the slurry composition of the present invention, it can exhibit excellent adhesiveness and water removal properties.
[0212] In addition, the positive electrode composite material layer of the positive electrode of the present invention is formed using the slurry composition of the present invention with excellent dispersibility, and thus has a uniform structure. Therefore, the positive electrode of the present invention has a positive electrode composite material layer with a uniform structure and excellent water removal properties, so that the internal resistance of the secondary battery can be reduced.
[0213] <Current collector>
[0214] As the current collector, a material having electrical conductivity and electrochemical durability can be used. Specifically, as the current collector, a current collector composed of metal materials such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. can be used. In addition, these materials can be used alone or in combination of two or more in any ratio.
[0215] When manufacturing an electrode further including the conductive adhesive layer between the electrode composite material layer and the current collector, for example, a current collector with a conductive adhesive layer formed on a current collector substrate can be used as the current collector.
[0216] As the current collector substrate, for example, a current collector made of the above-mentioned metal material can be used.
[0217] The method for forming the conductive adhesive layer on the current collector substrate is not particularly limited. For example, a slurry composition (also referred to as "conductive adhesive") in which at least a conductive material and an adhesive are dispersed or dissolved in a dispersion medium or solvent such as water, and a dispersant is also dispersed or dissolved arbitrarily, is applied to the current collector substrate and then dried, thereby forming the conductive adhesive layer.
[0218] The conductive material is not particularly limited, and for example, the conductive material that can be contained in the above-mentioned slurry composition can be used. In addition, as the binder, it is not particularly limited, and the granular polymer Y that can be contained in the above-mentioned slurry composition can be used. Furthermore, as the dispersant, it is not particularly limited, and for example, known dispersants such as carboxymethyl cellulose and its salts can be used.
[0219] The method of applying the conductive adhesive to the current collector substrate and the method of drying the applied conductive adhesive are not particularly limited, and known methods can be used.
[0220] <Positive electrode composite material layer>
[0221] The positive electrode composite material layer can be formed, for example, through the following steps: a step of applying the slurry composition on a current collector (coating step); and a step of drying the slurry composition applied on the current collector (drying step).
[0222] <<Coating process>>
[0223] As a method for applying the slurry composition to the current collector, it is not particularly limited, and a known method can be used. Specifically, as a coating method, a doctor blade method, an immersion method, a reverse roller method, a direct roller method, a gravure printing method, an extrusion method, a brush coating method, etc. can be used. At this time, the slurry composition can be applied only on a single side of the current collector, or it can be applied on both sides. In addition, the thickness of the slurry composition film on the current collector before drying after coating can be appropriately set according to the thickness of the positive electrode composite material layer obtained by drying.
[0224] <<Drying process>>
[0225] There is no particular limitation on the method for drying the slurry composition applied on the current collector, and a known method can be used, for example: a drying method using warm air, hot air, or low-humidity air; a vacuum drying method; a drying method using irradiation of infrared rays, electron beams, etc. In this way, by drying the slurry composition applied on the current collector, a positive electrode composite material layer can be formed on the current collector, and an electrode having a current collector and a positive electrode composite material layer can be obtained.
[0226] In addition, after the drying step, the electrode composite material layer may be subjected to a press treatment using a metal mold press or a roll press, etc. The press treatment can improve the peel strength of the electrode.
[0227] (Non-aqueous secondary battery)
[0228] The secondary battery of the present invention has the positive electrode of the present invention described above. For example, the secondary battery of the present invention has the positive electrode of the present invention described above, a negative electrode, a separator, and an electrolyte solution.
[0229] Furthermore, since the secondary battery of the present invention includes the positive electrode of the present invention, the internal resistance is reduced.
[0230] In addition, the following description will take a case where the nonaqueous secondary battery is a lithium ion secondary battery as an example, but the present invention is not limited to the following example.
[0231] <Negative electrode>
[0232] The negative electrode is not particularly limited, and a known negative electrode can be used.
[0233] <Spacer>
[0234] As a separator, there is no particular limitation, and examples thereof include: microporous membranes using resins of polyolefin series (polyethylene, polypropylene, polybutene, polyvinyl chloride); microporous membranes using resins such as polyethylene terephthalate, polycycloolefin, polyethersulfone, polyamide, polyimide, polyimide amide, polyaramid, polycycloolefin, nylon, polytetrafluoroethylene; fabrics or nonwoven fabrics using polyolefin fibers; aggregates of particles composed of insulating materials, etc. Among these, microporous membranes of resins of polyolefin series (polyethylene, polypropylene, polybutene, polyvinyl chloride) are preferably used from the perspective of being able to thin the overall film thickness of the separator, thereby increasing the ratio of the electrode composite material layer in the secondary battery and increasing the capacity per unit volume.
[0235] <Electrolyte>
[0236] As the electrolytic solution, an electrolytic solution obtained by dissolving an electrolyte in a solvent can be used.
[0237] Here, as a solvent, an organic solvent that can dissolve the electrolyte can be used. Specifically, as a solvent, it is preferred to use: carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), and ethyl methyl carbonate (EMC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as cyclopentane and dimethyl sulfoxide, etc. In addition, a mixed solution of these solvents can also be used. In addition, known additives such as vinylene carbonate (VC), fluoroethylene carbonate (FEC), methyl ethyl sulfone, etc. can also be added to the solvent.
[0238] As an electrolyte, a lithium salt can be used. As a lithium salt, for example, a compound described in Japanese Patent Publication No. 2012-204303 can be used. Among these lithium salts, LiPF6, LiClO4, and CF3SO3Li are preferred as electrolytes because they are easily soluble in organic solvents and show a high degree of dissociation. In addition, the electrolyte can be used alone or in combination of two or more in any ratio. Generally, there is a tendency that the higher the degree of dissociation of the supporting electrolyte, the higher the lithium ion conductivity, so the lithium ion conductivity can be adjusted according to the type of supporting electrolyte.
[0239] Moreover, the secondary battery of the present invention is not particularly limited and can be manufactured using known assembly methods. Specifically, the secondary battery of the present invention can be manufactured, for example, by the following manner: the positive electrode, negative electrode and separator of the present invention are wound, folded, etc. according to the shape of the battery as needed, placed in a battery container, and an electrolyte is injected into the battery container for sealing. Here, in order to prevent the rise of the internal pressure of the secondary battery, overcharge and discharge, etc., as needed, overcurrent protection elements such as fuses, PTC elements, porous metal mesh, guide plates, etc. can also be provided. In addition, the shape of the secondary battery can be any one of a coin type, a button type, a sheet type, a cylindrical type, a square type, a flat type, etc.
[0240] In addition, the battery components such as the positive electrode, negative electrode and separator of the secondary battery are usually arranged in the following manner: the positive electrode is connected to one side of the separator, and the negative electrode is connected to the other side of the separator. More specifically, the positive electrode composite material layer is connected to one side of the separator, and the negative electrode composite material layer is connected to the other side of the separator.
[0241] Example
[0242] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In addition, in the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.
[0243] In a polymer obtained by polymerizing a plurality of monomers, unless otherwise specified, the content ratio of a monomer unit formed by polymerization of a certain monomer in the polymer generally corresponds to the ratio (feed ratio) of the certain monomer in all monomers used for polymerization of the polymer.
[0244] Then, various measurements and evaluations were performed according to the following methods.
[0245] <Content of weakly acidic groups on the surface of carbon-coated olivine-type LFP particles>
[0246] <<Quantification of the total content of strong acidic groups, medium acidic groups, and weak acidic groups>
[0247] Weigh 3 g of carbon-coated olivine LFP particles as a sample in a container, add 30 mL of 0.01 M tetrabutylammonium hydroxide methyl isobutyl ketone (MIBK) solution, and seal it. Place the container in an ultrasonic cleaner, adjust the tank temperature to below 35°C, and perform ultrasonic dispersion treatment for 1 hour. Place the obtained dispersion in a centrifuge, and use a syringe filter to filter the obtained supernatant. Separate a portion of the obtained filtrate and titrate (back titration) with a 0.01 M perchloric acid standard solution. The acid amount A1 is calculated based on the difference between the obtained titration amount and the titration amount in the blank test. The above blank test is performed as follows: the carbon-coated olivine LFP particles as a sample are not placed in the container, except that the same operation as above is performed. The acid amount A1 is equivalent to the total content of strong acid groups, medium acid groups, and weak acid groups contained on the surface of the carbon-coated olivine LFP particles.
[0248] <<Quantification of the total content of strong acidic groups and medium acidic groups>>
[0249] Weigh 3 g of carbon-coated olivine LFP particles as a sample in a container, add 30 mL of 0.01 M tetraethylamine MIBK solution, and seal it. Place the container in an ultrasonic cleaner, adjust the tank temperature to below 35°C, and perform ultrasonic dispersion treatment for 1 hour. Place the obtained dispersion in a centrifuge, and use a syringe filter to filter the obtained supernatant. Separate a portion of the obtained filtrate and titrate it with a 0.01 M perchloric acid standard solution (back titration). The acid amount A2 is calculated based on the difference between the obtained titration amount and the titration amount in the blank test. The above blank test is performed as follows: the carbon-coated olivine LFP particles as a sample are not placed in the container, except that the same operation as above is performed. The acid amount A2 is equivalent to the total content of strong acid groups and medium acid groups contained on the surface of the carbon-coated olivine LFP particles.
[0250] <<Calculation of the content of weakly acidic groups>>
[0251] Then, the content of the weakly acidic groups on the surface of the carbon coating layer-coated olivine-type LFP particles is determined by subtracting the acid amount A2 from the acid amount A1.
[0252] <G / D ratio of carbon coating>
[0253] The G / D ratio of the carbon coating of the olivine-type lithium iron phosphate particles coated with the carbon coating was determined by microscopic laser Raman spectroscopy at 1600 cm -1 The peak intensity of the G band from the graphite structure detected near 1350 cm -1The ratio of the peak intensity of the D band derived from the crystal defect detected nearby was calculated from this. In addition, the microscopic laser Raman spectroscopy analysis was performed under the following measurement conditions.
[0254] <<Measurement conditions>>
[0255] Excitation wavelength: 532nm;
[0256] Grating: 600gr / mm;
[0257] Objective lens: magnification ×20, numerical aperture (NA) 0.45;
[0258] Wavelength range: 500cm -1 ~2850cm -1 ;
[0259] Apparatus used: RAMAN-11 (manufactured by Nanophoton Corporation).
[0260] <Weight average molecular weight and molecular weight distribution>
[0261] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the obtained polymer X were measured using gel permeation chromatography (GPC), and the molecular weight distribution (Mw / Mn) was calculated.
[0262] In addition, the eluent (0.1 M Tris buffer (pH 9, 0.1 M KCl)) was prepared as follows.
[0263] 1) Prepare 0.8 L of ultrapure water and dissolve 12.11 g of tris(hydroxymethyl)aminomethane and 7.46 g of potassium chloride.
[0264] 2) 0.1 M hydrochloric acid was added dropwise to adjust the pH to 9.
[0265] 3) After adjusting the pH, add ultrapure water to a volumetric flask until the liquid volume becomes 1 L.
[0266] The sample was prepared as follows.
[0267] First, polymer X was added to 5 mL of the eluent so that the solid content concentration became 0.05 wt%, and a stirring bar was added at 25° C. The mixture was stirred at 300 rpm using a magnetic stirrer for 30 minutes. The obtained solution was filtered through a 0.45 μm membrane filter and the filtrate was used as a measurement sample.
[0268] The measurement conditions of GPC are as follows.
[0269] Apparatus: Agilent 1260 Infinity II HPLC (Agilent Technologies);
[0270] Chromatographic column: TSKgel GMPWXL 13μm 300mm×7.8mm;
[0271] Elution buffer: 0.1 M Tris buffer (pH 9, 0.1 M KCl);
[0272] Flow rate: 0.7mL / min;
[0273] Detector: 1260 Infinity II RI detector (Agilent Technologies);
[0274] Column temperature: 40°C;
[0275] Injection volume: 200 μL;
[0276] Molecular weight standard: standard polyethylene oxide (PEO);
[0277] Sample concentration: 0.05 wt% (solid content concentration).
[0278] <Dispersibility of slurry composition>
[0279] According to JIS Z8803:1991, the viscosity of the positive electrode slurry composition was measured using a single cylindrical rotational viscometer (Brookfield B-type viscometer) at a rotation speed of 60 rpm and a temperature of 25°C, and it was confirmed to be within the range of 2500 mPa·s to 3500 mPa·s. According to the following criteria, the dispersibility of the positive electrode slurry composition is evaluated based on the value of the solid content concentration of the positive electrode slurry composition with a viscosity in the above range. In addition, in the same type of slurry composition, the larger the value of the solid content concentration in the same viscosity range (2500 mPa·s to 3500 mPa·s), the better the solid content contained in the slurry composition is dispersed, that is, the more excellent the dispersibility of the slurry composition.
[0280] A: Solid content concentration is 50% or more;
[0281] B: Solid content concentration is 45% or more and less than 50%;
[0282] C: Solid content concentration is 40% or more and less than 45%;
[0283] D: Solid content concentration is less than 40% or not dispersed (no fluidity).
[0284] <Adhesion of positive electrode composite material layer>
[0285] The positive electrode for lithium-ion secondary battery is cut into a rectangle of 1.0cm in width × 10cm in length as a test piece. After a transparent tape (transparent tape specified in JIS Z1522) is pasted on the surface of the positive electrode composite material layer side of the test piece, the stress when the transparent tape is peeled off from one end of the test piece at a speed of 50mm / minute in a 90° direction is measured. A total of three measurements are made, and the average value is calculated, which is used as the peel strength (N / m) and evaluated according to the following benchmarks. The greater the peel strength, the better the adhesion of the positive electrode composite material layer, and the more firmly it fits with the current collector.
[0286] A: Peel strength is 20N / m or more;
[0287] B: Peel strength is 15 N / m or more and less than 20 N / m;
[0288] C: Peel strength is 10 N / m or more and less than 15 N / m;
[0289] D: Peel strength is less than 10 N / m.
[0290] <Water removal properties of positive electrode composite material layer>
[0291] After the positive electrode for lithium-ion secondary batteries was vacuum dried at 120°C for 10 hours, it was placed at a temperature of 25°C, a dew point of -60°C, and a humidity of 0.05% for 10 minutes. Afterwards, the positive electrode composite material layer of the positive electrode for lithium-ion secondary batteries was weighed so that the weight became 0.1 to 0.2g, and the moisture content was determined by the Karl Fischer method using a coulometric titration moisture meter (manufactured by Mitsubishi Chemical Analytical Science Co., Ltd.). AQUAMICRON AX was used as the anolyte, AQUAMICRON CXU was used as the cathode liquid, and the vaporization temperature was set to 170°C. In addition, the determination of the water content was repeated three times, and the average value of the obtained values was taken as the measured value. Then, according to the following criteria, the dehydration of the positive electrode composite material layer was evaluated according to the measured value of the water content. In addition, the smaller the measured value of the water content, the better the dehydration of the positive electrode composite material layer.
[0292] A: 500ppm or less;
[0293] B: 500ppm or more and less than 600ppm;
[0294] C: 600ppm or more and less than 700ppm;
[0295] D: 700ppm or more.
[0296] <Internal resistance>
[0297] The lithium-ion secondary battery is charged to 50% of SOC (State Of Charge) at 1C (C is the value represented by the rated capacity (mA) / 1 hour (h)) in an atmosphere of 25°C. Afterwards, in an environment of 25°C, 50% of SOC is taken as the center, and charging and discharging are performed for 20 seconds at 0.2C, 0.5C, 1.0C, 2.0C, and 3.0C, respectively. The battery voltage after 20 seconds in each case (charging side and discharging side) is plotted against the current value, and its slope is obtained as the IV resistance (Ω) (IV resistance during charging and IV resistance during discharging). The obtained IV resistance value (Ω) is evaluated according to the following criteria. The smaller the value of IV resistance, the smaller the internal resistance of the lithium-ion secondary battery.
[0298] A: IV resistance is less than 10Ω;
[0299] B: IV resistance is greater than 10Ω and less than 15Ω;
[0300] C: IV resistance is greater than 15Ω and less than 20Ω;
[0301] D: IV resistance is 25Ω or more.
[0302] (Production Example 1)
[0303] Carbon coating-coated olivine-type LFP particles A are obtained by forming a carbon coating on the surface of olivine-type LFP particles by a solid phase method.
[0304] The weakly acidic group content of the obtained carbon coating layer-coated olivine LFP particles A was 10 μmol / g, and the G / D ratio of the carbon coating layer of the carbon coating layer-coated olivine LFP particles A was 0.69. The average particle size of the carbon coating layer-coated olivine LFP particles A was 1 μm.
[0305] (Production Example 2)
[0306] The carbon coating-coated olivine LFP particles A obtained in Production Example 1 were sintered at 400° C. in an oxygen (O 2 ) atmosphere to obtain carbon coating-coated olivine LFP particles B.
[0307] The weakly acidic group content of the obtained carbon coating layer-coated olivine LFP particles B was 13.5 μmol / g, and the G / D ratio of the carbon coating layer of the carbon coating layer-coated olivine LFP particles B was 0.676. The average particle size of the carbon coating layer-coated olivine LFP particles B was 1 μm.
[0308] (Production Example 3)
[0309] The carbon coating-coated olivine LFP particles A obtained in Production Example 1 were sintered at 700° C. in a nitrogen (N 2 ) atmosphere to obtain carbon coating-coated olivine LFP particles C.
[0310] The weakly acidic group content of the obtained carbon coating layer-coated olivine LFP particles C was 5 μmol / g, and the G / D ratio of the carbon coating layer of the carbon coating layer-coated olivine LFP particles C was 0.741. The average particle size of the carbon coating layer-coated olivine LFP particles C was 1 μm.
[0311] (Comparative Manufacturing Example 1)
[0312] Carbon-coated olivine LFP particles A obtained in Preparation Example 1 were fired at 700° C. in a nitrogen (N2) atmosphere to obtain carbon-coated olivine LFP particles D. The firing in the nitrogen atmosphere was performed for a longer time than the firing in the nitrogen atmosphere in Preparation Example 3.
[0313] The weakly acidic group content of the obtained carbon coating layer-coated olivine LFP particles D was 4.5 μmol / g, and the G / D ratio of the carbon coating layer of the carbon coating layer-coated olivine LFP particles D was 0.752. The average particle size of the carbon coating layer-coated olivine LFP particles D was 1 μm.
[0314] (Comparative Manufacturing Example 2)
[0315] The carbon coating-coated olivine LFP particles A obtained in Production Example 1 were calcined at 400° C. in an oxygen (O 2 ) atmosphere to obtain carbon coating-coated olivine LFP particles E. The calcination in the oxygen atmosphere was performed for a longer time than the calcination in the oxygen atmosphere in Production Example 2.
[0316] The weakly acidic group content of the obtained carbon coating layer-coated olivine LFP particles E was 17 μmol / g, and the G / D ratio of the carbon coating layer of the carbon coating layer-coated olivine LFP particles E was 0.6667. The average particle size of the carbon coating layer-coated olivine LFP particles E was 1 μm.
[0317] (Example 1)
[0318] <Preparation of aqueous solution of polymer X>
[0319] 770 parts of ion exchange water were added to a 10L flask with a rubber stopper, the temperature was heated to 40°C, and the flask was replaced with nitrogen at a flow rate of 100 mL / min. Next, 8 parts of acrylic acid as an ethylenically unsaturated carboxylic acid monomer, 17 parts of 2-hydroxyethyl methacrylate (HEMA) as a hydroxyl-containing methacrylate monomer, and 75 parts of 2-hydroxyethyl acrylate (β-HEA) as a hydroxyl-containing acrylate monomer were mixed and injected into the flask with a syringe. After that, 3 parts of a 10.0% aqueous solution of sodium L-ascorbate as a polymerization accelerator were added with a syringe. After 10 minutes, 38 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator were added to the flask with a syringe. One hour after the reaction started, the temperature was raised to 55°C to promote the polymerization reaction. After 2 hours, 0.5 parts of a 10.0% aqueous solution of sodium bisulfite as a polymerization accelerator was added by syringe, and 10 minutes later, 5 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator was added to the flask by syringe. After 3 hours, 0.5 parts of a 10.0% aqueous solution of sodium bisulfite as a polymerization accelerator was added by syringe, and 10 minutes later, 5 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator was added to the flask by syringe. After 4 hours, 0.5 parts of a 10.0% aqueous solution of sodium bisulfite as a polymerization accelerator was added by syringe, and 10 minutes later, 5 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator was added to the flask by syringe. After 5 hours, 0.5 parts of a 10.0% aqueous solution of sodium bisulfite as a polymerization accelerator was added by syringe, and 10 minutes later, 5 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator was added to the flask by syringe. After 6 hours, a reaction terminator was added, and the flask was opened to air to terminate the polymerization reaction. Thereafter, the pH of the product was adjusted to 8 using an 8% aqueous solution of lithium hydroxide, thereby obtaining an aqueous solution of polymer X.
[0320] In addition, the polymerization conversion rate of the monomers in the above-mentioned polymerization reaction is about 100%, and the composition of the obtained polymer X (the content ratio of each monomer unit) is the same as the ratio (feed ratio) of each monomer in the total monomers used for the polymerization of the polymer X. In addition, the obtained polymer X is water-soluble as defined in this specification.
[0321] <Preparation of granular polymer Y>
[0322] A hydrophilic group-containing acrylic polymer as the particulate polymer Y was prepared as follows.
[0323] In a 1L flask (reaction container) with a rubber stopper and a stirrer, 90 parts of ion exchange water and 0.5 parts of sodium lauryl sulfate as an emulsifier were added, the gas phase was replaced with nitrogen, and after heating to 60°C, 0.3 parts of ammonium persulfate (APS) as a polymerization initiator was dissolved in 20.0 parts of ion exchange water and added.
[0324] On the other hand, another container (emulsion container) was used to mix 30 parts of ion exchange water, 0.5 parts of sodium lauryl sulfate as an emulsifier, 76 parts of 2-ethylhexyl acrylate as a (meth) acrylate monomer, 2.0 parts of itaconic acid as a carboxylic acid group-containing monomer, 1.0 parts of 2-hydroxyethyl acrylate (β-HEA) as a hydroxyl group-containing monomer, and 21 parts of acrylonitrile as a nitrile group-containing monomer to obtain a monomer composition. The monomer composition was continuously added to the above-mentioned 1L flask with a rubber stopper for 3 hours to perform polymerization. During the addition, the reaction was carried out at 60°C. After the addition was completed, it was further stirred at 80°C for 2 hours.
[0325] A 5% sodium hydroxide aqueous solution was added to the aqueous dispersion containing the polymer obtained above, and the pH was adjusted to 8 to obtain an aqueous dispersion of particulate polymer Y (hydrophilic group-containing acrylic polymer).
[0326] <Preparation of CNT dispersion>
[0327] 0.4 parts of carbon nanotubes (BET specific surface area: 250 m 2 / g), 0.6 parts (solid content conversion amount) of carboxymethyl cellulose ("Daicel 1220" manufactured by Daicel Corporation) and 99 parts of ion exchange water, and then, using a bead mill using zirconia beads with a diameter of 1 mm, mixing at a peripheral speed of 8 m / s for 1 hour to prepare a CNT dispersion with a solid content concentration of 1 mass%.
[0328] <Preparation of acetylene black dispersion>
[0329] 4.4 parts of acetylene black as a conductive material, 0.6 parts (solid content conversion amount) of carboxymethyl cellulose ("Daicel 1220" manufactured by Daicel Corporation), and 95 parts of ion-exchanged water were stirred using a disperser (3000 rpm, 60 minutes) to prepare an acetylene black dispersion having a solid content concentration of 5% by mass.
[0330] <Preparation of positive electrode slurry composition>
[0331] Add 100 parts of carbon-coated olivine LFP particles A (surface weakly acidic group content: 10 μmol / g, G / D ratio of carbon coating: 0.69, average particle size: 1 μm) as the positive electrode active material, 1.2 parts (equivalent amount of solid content) of aqueous solution of polymer X and ion exchange water, adjust the solid content concentration to 78%, and mix with a planetary mixer (60 rpm, 50 minutes).
[0332] Next, acetylene black dispersion is added in an amount of 1.9 parts of acetylene black, and mixed with a planetary mixer (60 rpm, 10 minutes). Next, CNT dispersion is added in an amount of 0.1 parts of carbon nanotubes, and mixed with a planetary mixer (60 rpm, 10 minutes). Finally, 1.8 parts (equivalent to the solid content) of an aqueous dispersion of particulate polymer Y is added, mixed with a planetary mixer (40 rpm, 10 minutes) to prepare a positive electrode slurry composition. In addition, when preparing a positive electrode slurry composition, water is added to adjust the viscosity of the obtained positive electrode slurry composition (measured by a single cylindrical rotational viscometer (Brookfield B-type viscometer) according to JIS Z8803:1991. Temperature: 25°C, rotation speed: 60 rpm) in the range of 2500 mPa·s to 3500 mPa·s.
[0333] The dispersibility of the obtained slurry composition for positive electrode was evaluated. The results are shown in Table 1.
[0334] <Preparation of current collector with conductive adhesive layer>
[0335] As a current collector for producing the positive electrode, a current collector with a conductive adhesive layer prepared by the following method was used.
[0336] 70 parts of conductive carbon (graphite / acetylene black = 70 / 30 (mass ratio)) and 8 parts of carboxymethyl cellulose as a dispersant ("Daicel 1220" manufactured by Daicel Corporation) were added, and after stirring at 3000 rpm for 60 minutes using a disperser, 22 parts of an aqueous dispersion of granular polymer Y in terms of solid content were added, and further stirred at 1500 rpm for 10 minutes using a disperser to prepare a conductive adhesive.
[0337] The conductive adhesive was applied to the aluminum foil as the current collector substrate by a casting method using a roll bar at a molding speed of 20 m / min, and dried at 80° C. to form a conductive adhesive layer with a thickness of 1 μm. Thus, a current collector with a conductive adhesive layer formed on the current collector substrate was obtained.
[0338] <Manufacturing of positive electrodes for lithium-ion secondary batteries>
[0339] The coating was applied using a comma coater so that the weight per unit area after drying was 22 mg / cm 2 The positive electrode slurry composition obtained as described above was applied to the conductive adhesive layer side of the current collector with a conductive adhesive layer, dried at 90°C for 20 minutes, further dried at 120°C for 20 minutes, and then heated at 60°C for 10 hours to obtain a positive electrode raw material. The positive electrode raw material was rolled by roller pressing to produce a positive electrode raw material having a density of 2.5 g / cm 3 The positive electrode sheet was formed by a positive electrode composite material layer, a conductive adhesive layer and an aluminum foil. Then, the positive electrode sheet was cut into a size of 48.0 mm in width and 47 cm in length to serve as a positive electrode for a lithium ion secondary battery.
[0340] The adhesiveness and water removal properties of the positive electrode composite material layer were evaluated using the obtained positive electrode for lithium ion secondary battery.
[0341] <Manufacturing of negative electrodes for lithium-ion secondary batteries>
[0342] In a 5 MPa pressure-resistant container equipped with a stirrer, 65 parts of styrene as an aromatic vinyl monomer, 35 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 2 parts of itaconic acid as an ethylenically unsaturated carboxylic acid monomer, 1 part of 2-hydroxyethyl acrylate as a hydroxyl-containing monomer, 0.3 parts of tert-dodecyl mercaptan as a molecular weight regulator, 5 parts of sodium dodecylbenzene sulfonate as an emulsifier, 150 parts of ion-exchanged water as a solvent and 1 part of potassium persulfate as a polymerization initiator were added, and after sufficient stirring, the temperature was raised to 55° C. to initiate polymerization.
[0343] When the monomer consumption reaches 95.0%, the reaction is terminated by cooling. A 5% sodium hydroxide aqueous solution is added to the aqueous dispersion containing the polymer thus obtained to adjust the pH to 8. Thereafter, the unreacted monomers are removed by heating and distilling under reduced pressure. Furthermore, the mixture is then cooled to below 30°C to obtain an aqueous dispersion of a particulate polymer as a binder material for the negative electrode.
[0344] In a planetary mixer, 48.75 parts of artificial graphite and 48.75 parts of natural graphite as negative electrode active materials, and 1 part (solid content equivalent) of carboxymethyl cellulose as a thickener were added. Furthermore, it was diluted with ion exchange water to make the solid content concentration 60%, and then mixed at a rotation speed of 45 rpm for 60 minutes. After that, 1.5 parts of an aqueous dispersion of a particulate polymer obtained as a binder for the negative electrode as described above was added in terms of solid content equivalent, and mixed at a rotation speed of 40 rpm for 40 minutes. Then, ion exchange water was added in such a way that the viscosity became 3000 ± 500 mPa·s (B-type viscometer, measured at 25°C and 60 rpm), thereby preparing a negative electrode slurry composition.
[0345] Use a comma coater to coat at a rate of 10 ± 0.5 mg / cm 2 The negative electrode slurry composition was applied on the surface of a copper foil having a thickness of 15 μm as a current collector. The copper foil coated with the negative electrode slurry composition was then conveyed in an oven at a temperature of 80° C. for 2 minutes at a speed of 400 mm / min and further conveyed in an oven at a temperature of 110° C. for 2 minutes, thereby drying the negative electrode slurry composition on the copper foil to obtain a negative electrode raw material having a negative electrode composite material layer formed on the current collector.
[0346] The negative electrode raw material was rolled by roller pressing to produce a material having a density of 1.6 g / cm 3 The negative electrode sheet was formed of a negative electrode composite material layer and a copper foil. Then, the negative electrode sheet was cut into pieces with a width of 50.0 mm and a length of 52 cm to serve as a negative electrode for a lithium ion secondary battery.
[0347] <Manufacturing of lithium-ion secondary batteries>
[0348] The electrode composite material layers of the positive electrode and the negative electrode of the lithium ion secondary battery are made relative to each other, and a spacer (microporous film made of polyethylene) with a thickness of 15 μm is placed between the two, and a core with a diameter of 20 mm is used for winding to obtain a wound body. Then, the obtained wound body is compressed from one direction at a speed of 10 mm / second to a thickness of 4.5 mm. In addition, the compressed wound body is elliptical in top view, and the ratio of its major diameter to minor diameter (major diameter / minor diameter) is 7.7.
[0349] In addition, as an electrolyte, a LiPF6 solution with a concentration of 1.0 M (containing a solvent: a mixed solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio), containing an additive: 2 volume % (solvent ratio) of vinylene carbonate) was prepared.
[0350] After that, the compressed winding body was stored in an aluminum laminated case together with 3.2 g of electrolyte. Then, a nickel lead was connected to a predetermined position of the negative electrode for the secondary battery and an aluminum lead was connected to a predetermined position of the positive electrode for the lithium-ion secondary battery, and the opening of the case was sealed by heat to obtain a lithium-ion secondary battery. The lithium-ion secondary battery was in the shape of a bag with a width of 35 mm, a height of 60 mm, and a thickness of 5 mm, and the nominal capacity of the battery was 700 mAh.
[0351] The internal resistance of the obtained lithium ion secondary battery was evaluated. The results are shown in Table 1.
[0352] (Example 2)
[0353] The granular polymer Y was prepared as follows. In addition, the aqueous solution of polymer X, the granular polymer Y, the CNT dispersion, the acetylene black dispersion, the positive electrode slurry composition, the current collector with a conductive adhesive layer, the positive electrode for lithium ion secondary battery, the negative electrode for lithium ion secondary battery, and the lithium ion secondary battery were prepared in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 1.
[0354] <Preparation of granular polymer Y>
[0355] A hydrophilic group-containing styrene-butadiene copolymer (hydrophilic group-containing SBR) as a particulate polymer Y was prepared as follows.
[0356] In a 5 MPa pressure-resistant container equipped with a stirrer, 63 parts of styrene as an aromatic vinyl monomer, 34 parts of 1,3-butadiene as a conjugated diene monomer, 2 parts of itaconic acid as a carboxylic acid group-containing monomer, 1 part of 2-hydroxyethyl acrylate as a hydroxyl group-containing monomer, 0.3 parts of tert-dodecyl mercaptan as a molecular weight regulator, 5 parts of sodium dodecylbenzene sulfonate as an emulsifier, 150 parts of ion-exchanged water as a solvent and 1 part of potassium persulfate as a polymerization initiator were added, and after sufficient stirring, the temperature was raised to 55° C. to initiate polymerization.
[0357] When the monomer consumption reaches 95.0%, the reaction is terminated by cooling. A 5% sodium hydroxide aqueous solution is added to the aqueous dispersion containing the polymer thus obtained to adjust the pH to 8. Thereafter, unreacted monomers are removed by heating and reduced pressure distillation. Furthermore, the mixture is then cooled to 30° C. or less to obtain an aqueous dispersion of a hydrophilic group-containing SBR as a granular polymer.
[0358] (Examples 3-4, 7-8, Comparative Examples 3-4)
[0359] When preparing an aqueous solution of polymer X, the type and / or amount of the monomer added was changed so that the composition of the obtained polymer X (the content ratio of each monomer unit) was as shown in Tables 1 to 2. In addition, the preparation of an aqueous solution of polymer X, the preparation of a granular polymer Y, the preparation of a CNT dispersion, the preparation of an acetylene black dispersion, the preparation of a slurry composition for a positive electrode, the preparation of a current collector with a conductive adhesive layer, the preparation of a positive electrode for a lithium ion secondary battery, the preparation of a negative electrode for a lithium ion secondary battery, and the preparation of a lithium ion secondary battery were carried out in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Tables 1 to 2.
[0360] (Example 5)
[0361] When preparing the slurry composition for the positive electrode, the carbon coating coated olivine LFP particles B (content of weakly acidic groups on the surface: 13.5 μmol / g, G / D ratio of the carbon coating: 0.676, average particle size: 1 μm) were used instead of the carbon coating coated olivine LFP particles A (content of weakly acidic groups on the surface: 10 μmol / g, G / D ratio of the carbon coating: 0.69, average particle size: 1 μm). In addition, the preparation of the aqueous solution of polymer X, the preparation of the granular polymer Y, the preparation of the CNT dispersion, the preparation of the acetylene black dispersion, the preparation of the slurry composition for the positive electrode, the preparation of the current collector with a conductive adhesive layer, the preparation of the positive electrode for the lithium ion secondary battery, the preparation of the negative electrode for the lithium ion secondary battery, and the preparation of the lithium ion secondary battery were carried out in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 1.
[0362] (Example 6)
[0363] When preparing the slurry composition for the positive electrode, the carbon coating coated olivine LFP particles C (content of weakly acidic groups on the surface: 5 μmol / g, G / D ratio of the carbon coating: 0.741, average particle size: 1 μm) were used instead of the carbon coating coated olivine LFP particles A (content of weakly acidic groups on the surface: 10 μmol / g, G / D ratio of the carbon coating: 0.69, average particle size: 1 μm). In addition, the preparation of the aqueous solution of polymer X, the preparation of particulate polymer Y, the preparation of CNT dispersion, the preparation of acetylene black dispersion, the preparation of the slurry composition for the positive electrode, the preparation of the current collector with a conductive adhesive layer, the preparation of the positive electrode for lithium ion secondary battery, the preparation of the negative electrode for lithium ion secondary battery and the preparation of lithium ion secondary battery were carried out in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 1.
[0364] (Example 9)
[0365] When preparing the positive electrode slurry composition, no CNT dispersion was added, and the amount of acetylene black dispersion was changed from 1.9 parts to 3.0 parts. In addition, the preparation of the aqueous solution of polymer X, the preparation of granular polymer Y, the preparation of acetylene black dispersion, the preparation of the positive electrode slurry composition, the preparation of the current collector with a conductive adhesive layer, the preparation of the positive electrode for lithium ion secondary battery, the preparation of the negative electrode for lithium ion secondary battery and the preparation of lithium ion secondary battery were carried out in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 2.
[0366] (Example 10)
[0367] When preparing the positive electrode slurry composition, acetylene black dispersion (equivalent to 1.9 parts of acetylene black) was not added, and the amount of CNT dispersion was changed from 0.1 parts to 0.5 parts of carbon nanotubes. In addition, the preparation of the aqueous solution of polymer X, the preparation of granular polymer Y, the preparation of CNT dispersion, the preparation of positive electrode slurry composition, the preparation of current collector with conductive adhesive layer, the preparation of positive electrode for lithium ion secondary battery, the preparation of negative electrode for lithium ion secondary battery and the preparation of lithium ion secondary battery were carried out in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 2.
[0368] (Comparative Example 1)
[0369] When preparing the slurry composition for the positive electrode, the carbon coating coated olivine LFP particles D (the content of weakly acidic groups on the surface: 4.5 μmol / g, the G / D ratio of the carbon coating: 0.6667, and the average particle size: 1 μm) were used instead of the carbon coating coated olivine LFP particles A (the content of weakly acidic groups on the surface: 10 μmol / g, the G / D ratio of the carbon coating: 0.69, and the average particle size: 1 μm). In addition, the preparation of the aqueous solution of polymer X, the preparation of particulate polymer Y, the preparation of CNT dispersion, the preparation of acetylene black dispersion, the preparation of the slurry composition for the positive electrode, the preparation of the current collector with a conductive adhesive layer, the preparation of the positive electrode for lithium ion secondary battery, the preparation of the negative electrode for lithium ion secondary battery, and the preparation of the lithium ion secondary battery were carried out in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 2.
[0370] (Comparative Example 2)
[0371] When preparing the slurry composition for the positive electrode, the carbon coating coated olivine LFP particles E (content of weakly acidic groups on the surface: 17 μmol / g, G / D ratio of the carbon coating: 0.6667, average particle size: 1 μm) were used instead of the carbon coating coated olivine LFP particles A (content of weakly acidic groups on the surface: 10 μmol / g, G / D ratio of the carbon coating: 0.69, average particle size: 1 μm). In addition, the preparation of the aqueous solution of polymer X, the preparation of the granular polymer Y, the preparation of the CNT dispersion, the preparation of the acetylene black dispersion, the preparation of the slurry composition for the positive electrode, the preparation of the current collector with a conductive adhesive layer, the preparation of the positive electrode for the lithium ion secondary battery, the preparation of the negative electrode for the lithium ion secondary battery, and the preparation of the lithium ion secondary battery were carried out in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 2.
[0372] In addition, in Tables 1 and 2 shown below,
[0373] "AA" represents acrylic acid unit,
[0374] "NaSS" means sodium styrene sulfonate unit,
[0375] "β-HEA" means 2-hydroxyethyl acrylate unit,
[0376] "HEMA" means 2-hydroxyethyl methacrylate units,
[0377] "Aamid" means acrylamide unit,
[0378] "AN" stands for acrylonitrile unit,
[0379] "ACR" means acrylic polymer containing hydrophilic groups.
[0380] "SBR" means styrene-butadiene copolymer containing hydrophilic groups.
[0381] "CNT" stands for carbon nanotube,
[0382] "AcB" stands for acetylene black.
[0383] In Table 1, the description "AN / Aamid" of the type of other monomer units and the description "5 / 10" of the content ratio in the polymer X in Example 4 mean that the polymer X contains 5% by mass of acrylonitrile units and 10% by mass of acrylamide units.
[0384] [Table 1]
[0385]
[0386] [Table 2]
[0387]
[0388] As can be seen from Tables 1 to 2, the non-aqueous secondary battery positive electrode slurry compositions of Examples 1 to 10, which contain carbon coating-coated olivine-type LFP particles having a surface weakly acidic group content within a specified range and polymer X having a content ratio of acidic group-containing monomer units within a specified range, have excellent dispersibility, and the positive electrode composite material layer formed using the slurry composition can exhibit excellent adhesion and water removal properties.
[0389] On the other hand, it is found that the non-aqueous secondary battery positive electrode slurry composition of Comparative Example 1, which uses carbon coating-coated olivine-type LFP particles whose surface weakly acidic group content does not satisfy the specified range, has poor dispersibility, and the positive electrode composite material layer formed using the slurry composition has poor adhesion and water removal properties.
[0390] In addition, it is found that the non-aqueous secondary battery positive electrode slurry composition of Comparative Example 2, which uses a carbon coating layer to coat olivine-type LFP particles whose surface weakly acidic group content exceeds the specified range, has poor dispersibility, and the positive electrode composite material layer formed using the slurry composition has poor adhesion and dehydration properties.
[0391] Furthermore, it is found that the nonaqueous secondary battery positive electrode slurry composition of Comparative Example 3 using a polymer having an acidic group-containing monomer unit content ratio outside the prescribed range has poor dispersibility, and the positive electrode composite material layer formed using the slurry composition has poor adhesion and dehydration properties.
[0392] Furthermore, it is found that the nonaqueous secondary battery positive electrode slurry composition of Comparative Example 4 using a polymer whose content ratio of the acidic group-containing monomer unit does not satisfy the prescribed range has poor dispersibility, and the positive electrode composite material layer formed using the slurry composition has poor adhesion and dehydration properties.
[0393] Industrial Applicability
[0394] According to the present invention, it is possible to provide a non-aqueous secondary battery positive electrode slurry composition that has excellent dispersibility and can enable a positive electrode composite material layer to exhibit excellent adhesiveness and water removal properties.
[0395] Furthermore, according to the present invention, it is possible to provide a positive electrode for a non-aqueous secondary battery having a positive electrode composite material layer capable of exhibiting excellent adhesiveness and water-removing properties.
[0396] Furthermore, according to the present invention, a nonaqueous secondary battery having the nonaqueous secondary battery positive electrode can be provided.
Claims
1. A slurry composition for a positive electrode of a non-aqueous secondary battery, comprising: Carbon coating-coated olivine-type lithium iron phosphate particles in which at least a portion of the surface of the olivine-type lithium iron phosphate particles is coated with a carbon coating; and A polymer X containing 3% by mass or more and 40% by mass or less of an acidic group-containing monomer unit, The carbon coating layer covers the surface of the olivine-type lithium iron phosphate particles, and the content of the weakly acidic groups is 5 μmol / g or more and 15 μmol / g or less.
2. The non-aqueous secondary battery positive electrode slurry composition according to claim 1, wherein The carbon coating layer has a G / D ratio of 0.4 or more and 0.770 or less.
3. The slurry composition for a positive electrode of a non-aqueous secondary battery according to claim 1, wherein The acidic group-containing monomer unit contains at least one of a carboxylic acid group-containing monomer unit and a sulfonic acid group-containing monomer unit.
4. The slurry composition for a positive electrode of a non-aqueous secondary battery according to claim 1, wherein The polymer X further contains 55% by mass or more and 90% by mass or less of a hydroxyl group-containing acrylic acid ester monomer unit.
5. The slurry composition for a positive electrode of a non-aqueous secondary battery according to claim 1, wherein The weight average molecular weight of the polymer X is 50,000 or more and less than 500,000.
6. The slurry composition for a positive electrode of a non-aqueous secondary battery according to claim 1, wherein A particulate polymer Y containing a hydrophilic group is also included.
7. The slurry composition for a positive electrode of a non-aqueous secondary battery according to claim 6, wherein The content of the particulate polymer Y is 0.5 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the carbon coating layer-covered olivine-type lithium iron phosphate particles.
8. The slurry composition for a positive electrode of a non-aqueous secondary battery according to claim 1, wherein Also included is a conductive material comprising at least one of carbon nanotubes and a particulate conductive material. 9 . A positive electrode for a non-aqueous secondary battery, comprising a positive electrode composite material layer formed using the slurry composition for a non-aqueous secondary battery positive electrode according to claim 1 . 10 . A non-aqueous secondary battery comprising the positive electrode for a non-aqueous secondary battery according to claim 9 .
Citation Information
Patent Citations
Electrode for secondary battery, binder for secondary battery electrode, manufacturing method and secondary battery
JP2012204303A
Aqueous electrode binder for secondary battery
WO2012008539A1